Pest diversity and their environmental drivers on cashew plantations in Guinea-Bissau - Paola Sierra-Baquero; Sílvia Catarino; Gonçalo J. Costa; Zinha Correia; Maria Rosa Ferreira; Elsa Borges da Silva; Maria Cristina Duarte; Maria M. Romeiras; Edgar Varón-Devia; Luís Catarino; Filipa Monteiro (Agriculture, Ecosystems & Environment, 2026)

Aqua training promotes changes of skeletal muscle mass in show jumping horses - C. Nascimento; C. Santos; M. Walton; T. Gonçalves; G. Freire; M. Nicolau; F. Silvestre; J. Simões; J. Borges; N. Pires; H. Manso Filho; H. Clayton; et al. (Journal of Equine Veterinary Science, 2026)

High-efficiency phosphorus removal from real wastewater using ZnAl-layered double hydroxides: Performance and limitations - Inês D. Borges; Frederico Maia; Carlos M. Silva; Margarida J. Quina (Chemosphere, 2026)

Meteorology, turbulence and indoor–outdoor air quality relationships in two public buildings in Madrid - J.M. Cordero; A. Narros; R. Borge; Andrés Núñez; Ana M. García; E. Díaz-Ramiro; E. Alonso-Blanco; J. Fernández; F.J. Gómez-Moreno; B. Artíñaño; C. Román-Cascón; M. Sastre; et al. (Atmospheric Pollution Research, 2026)

Global invasion dynamics of the charru mussel Mytella strigata (Hanley, 1843): mechanisms, impacts, knowledge gaps, and biosecurity implications - Paravanparambil Rajakumar Jayachandran; Pei-Zhen Ma; Marcel Velásquez; Broc S. Kokesh; Mantodi Jima; Kaent Immanuel N. Uba; César Lodeiros; Naduvilakkandy Vishnudattan; Luiza Costa Mello; Rafael Metri; Pablo Damian Borges Guilherme; Pablo Muniz; et al. (Hydrobiologia, 2026)

Desertification reshapes soil fungal community structure across Brazilian dryland ecoregions - Ruggeri M.M. Santos; Katriny K.S. Negreiros; Ademir S.F. Araujo; Erika V. de Medeiros; George R. Lambais; Rodrigo S. Macedo; Raphael M. Beirigo; Diogo P. Costa; Kaio G.V. Garcia; Antonio Y.V. Lima; Gabriel N. Nóbrega; Lucas W. Mendes; et al. (Applied Soil Ecology, 2026)

Toxic blooms: from Joseph Dalton Hooker and Asa Gray to giant honeybees and mad honey - Renee M Borges (Journal of Biosciences, 2026)

Who funds science and its publication? Does it matter? - Renee M Borges (Journal of Biosciences, 2026)

Group size and composition of brown howler monkeys (Alouatta guariba) in three fragments of Araucaria Pine Forest in southern Brazil - Amanda Letícia Borges; Gabriel Rangel Santos-Mariano; Pedro Augusto Andrich Mota; Samuel Barbarine da Silva; Mário Retondo; Lucas M. Aguiar (Primates, 2026)
Brown howler monkeys ( Alouatta guariba ) are increasingly threatened by habitat loss, sylvatic yellow fever, and negative human interactions. In southern Brazil, brown howlers still inhabit some fragments of the endangered Araucaria Pine Forest (APF), but basic information on their social organization remains scarce. We surveyed brown howler monkey groups to assess their group size and composition in three nearby similarly sized peri-urban APF fragments in Curitiba, southern Brazil. Using Generalized Linear Mixed Models, we investigated whether the number of males, females and immatures could be predicted by the number of individuals in each of these sex-age categories, along with group size. Monthly expeditions were conducted over 11–13 months, using multiple walks in each fragment to survey howler monkeys’ groups. We surveyed 17 groups over 332 km of fieldwork. Group sizes ranged from two to eight individuals (mean 4.88 ± 1.65 SD), sex and age proportion was 1 adult male: 0.5 subadult male: 1.7 adult females: 1.2 juvenile: 0.4 infant, and the immature-to-female ratio was 0.96. We found that group size was a significant positive predictor for the number of adult females, juveniles and immatures overall, suggesting a general increase in fitness in larger groups, but not for the number of males and infants. Our findings indicate the presence of a small established population of brown howler monkeys in relatively small APFs, with population parameters in the typical range of the species, but an immature-to-female ratio more similar to populations of stagnanting growth, pointing to the necessity to implement measures to conserve and connect this population in an endangered habitat.

Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

Habitat Suitability for a Unique, Fully Marine American Manatee ( Trichechus manatus ) Population Primarily Depends on Presence of Submarine Freshwater Springs - A. C. O. Meirelles; I. C. Normande; M. D. O. Alves; K. F. Choi; V. L. Carvalho; J. C. G. Borges; L. von Fersen; Andrew W. Trites (Marine Mammal Science, 2026)
The American manatee ( Trichechus manatus ) requires freshwater mainly from rivers and springs to maintain osmoregulatory balance in saline environments. However, in Brazil's semi‐arid Potiguar Basin, manatees now rely solely on submarine freshwater springs because hypersaline estuaries have become unsuitable sources of freshwater. We applied MaxEnt modeling to presence‐only data (sightings and filtered telemetry records) to produce habitat suitability maps and identify the environmental conditions driving habitat use. Telemetry locations were spatially and temporally thinned and subsampled to balance individual contributions, and alternative thinning scenarios were evaluated—while the model with the lowest level of spatial filtering showing the most stable performance was retained for inference. Model performance and fit were high (AUC = 0.979; CBI = 0.943, training gain = 2.76), and model suitability was strongly structured by proximity to submarine springs, with predicted probability declining sharply beyond 4–8 km. Seagrass presence contributed secondarily to suitability, whereas the other variables showed limited independent explanatory power at the regional scale. Suitable habitat was highly localized, comprising approximately 4% (301 km 2 ) of the modeled coastal area and concentrated near Icapuí (Ceará) and Areia Branca (Rio Grande do Norte). These findings reveal the strong ecological constraints shaping this fully marine manatee population and highlight the critical role of submarine freshwater springs and seagrass meadows in sustaining manatee presence in hypersaline coastal systems. Protecting these key resources is essential for conservation planning in a region facing increasing freshwater limitation and expanding offshore development.

Microplastic characterization and abundance in stomach contents of the American crocodile (Crocodylus acutus) from Cozumel, Mexico - Diana Marcela Caro-Martínez; Carlos Alberto Niño-Torres; Jaime Rendón-von Osten; Delma Nataly Castelblanco-Martínez; Lorena M. Rios-Mendoza; Oscar Frausto-Martínez; Maria del Pilar Blanco-Parra; Merle Marisa Borges-Ramírez; Pierre Charruau (Regional Studies in Marine Science, 2026)

Microplastic Interaction in the Parasite Infection of Commercial Marine Puffer Fishes (Tetraodontiformes: Tetraodontidae) of the Campeche Coast, Mexico - Ana Luisa May-Tec; Juan Pablo Ek-Huchim; Edgar Fernando Mendoza-Franco; Jaime Navarro-Flores; Jaime Rendón-Von Osten; Merle M. Borges-Ramírez (Acta Parasitologica, 2026)

Birds and bees do not express RAGE: comparative physiology and non-conventional model organisms hold the key to hyperglycemia tolerance - Renee M Borges (Journal of Biosciences, 2026)

Modeling juvenile discards of goliath catfish (Brachyplatystoma vaillantii) at the mouth of the Amazon River: can high-discard events be predicted? - Diego Gomes Trindade; Adauto dos Santos Mello-Filho; Luiza Prestes; Davi Butturi-Gomes; Matheus Silva de Almeida; Fúlvio A. M. Freire; Ronaldo Borges Barthem; Bianca Bentes (Frontiers in Marine Science, 2026)
Introduction This study investigates the size composition of Brachyplatystoma vaillantii specimens caught by the Amazon industrial fleet, identifying spatiotemporal patterns and assessing the vulnerability of juveniles to fishing. Methods The research was conducted at the Amazon River mouth, using data collected by onboard scientific observers between 2008 and 2011, including catch records and length sampling of goliath catfish. Statistical analysis employed spatiotemporal vector autoregressive mixed models, using the proportion of discarded fish as the response variable. Results The average discard rate was 22.7% in number and 9.4% in biomass. Statistical analysis revealed significant differences in discarded rates among fishing seasons (FS), with FS-C (2010–2011) showing the highest rates. Environmental and operational variables, such as river discharge, depth, trawl speed, and geographical location, significantly influenced discarded rates. River discharge had a positive linear effect on discards, whereas depth had a negative effect, indicating higher discarded rates in shallow waters. Spatial and temporal autocorrelation were significant, highlighting the importance of modeling these components to understand discard patterns. Discussion The analysis suggested that, despite spatial and temporal variability, fishing season and environmental conditions, such as depth and discharge, are key determinants of juvenile discard. The study underscores the need for more sophisticated models to capture the complex dynamics of discards and to support the identification of high-risk areas and seasons for juvenile catches, thereby supporting the design of more effective spatial and temporal fisheries regulations.

Toxic nanoparticles in Amazon River sediments: Microscopy and satellite-based assessment - Emanuelle Goellner; Brian William Bodah; Alcindo Neckel; Paloma Carollo Toscan; Júlia M. Scopel; M. Santosh; Guilherme Peterle Schmitz; Giana Mores; Marcos L.S. Oliveira; Eduardo Nuno Borges Pereira (Marine Pollution Bulletin, 2026)

Historical and elevational contamination by toxic metals and arsenic in hummingbirds in southeastern Mexico: a variable to consider in the face of the global pollinator crisis - Ruth Partida-Lara; Paula L. Enríquez; José Raúl Vázquez-Pérez; Merle M. Borges-Ramírez; Marina Esperanza Rodríguez-Yah; Jaime Rendón-von Osten (Environmental Research, 2026)

Dominant effects of the antiepileptic drug carbamazepine over climate change stressors on Mytilus galloprovincialis toxicity - Farhat-Un-Nisá N. Bajwa; Marta Cunha; Juliano M. Vilke; Bruno D.D. Fragoso; Rodrigo Borges; Amadeu M.V.M. Soares; Rosa Freitas; Tainá G. Fonseca (Marine Pollution Bulletin, 2026)

Divergent metabolic strategies in two Aphanothece species (Cyanobacteria): Interactive effects of temperature and light intensity on growth, pigment composition, and lipid profile - Ronald Tarazona Delgado; Rui dos Santos Ferreira Filho; Mariana F. G. Assunção; Berk Aksoy; Lília M. A. Santos; Carlos Rafael Borges Mendes (Journal of Applied Phycology, 2026)
Temperature and light intensity are among the most influential environmental factors modulating cyanobacterial physiology, yet their interactive effects on metabolite accumulation remain understudied in several genera with biotechnological potential. In this study, the influence of temperature (12, 20 and 28 °C) and light intensity (60, 120 and 180 µmol photons m −2 s −1 ) on the growth, pigment profile, and lipid composition of two Aphanothece strains ( A. microscopica and A. stagnina ) was evaluated through a 3 2 full factorial design. Both species exhibited strain-specific responses across all measured parameters. In A. microscopica , high temperature and low light promoted the accumulation of chlorophyll a , phycobiliproteins (particularly phycocyanin and allophycocyanin), and a diversified carotenoid profile including echinenone and myxoxanthophyll. In contrast, A. stagnina showed higher pigment productivity under high temperature combined with high irradiance, particularly enriching zeaxanthin and β-carotene. Lipid content increased in both strains under low temperature and moderate light, suggesting a compensatory metabolic route under suboptimal growth conditions. Fatty acid analysis revealed major differences: A. microscopica displayed a complex profile dominated by palmitic acid and enriched with polyunsaturated fatty acids under cold treatments, while A. stagnina exhibited reduced diversity, with monounsaturated fatty acids, especially palmitoleic and myristic acids, prevailing under all conditions. These findings underscore the metabolic flexibility of Aphanothece species in response to environmental variation and highlight their differentiated potential for applications in biorefineries. Selective cultivation of each strain under tailored conditions may enhance the yield of specific pigments or lipids, supporting their use in biofuel, nutraceutical, and cosmeceutical industries. Graphical Abstract

Precision by design: Surface plasmon resonance and the integration of biophysics in fragment-based drug discovery - Todd W. Pascarella; Jeremiah S. Joseph; Jason M. Newman; Júlio C. Borges; Paulo R. Dores-Silva (Biophysical Reviews, 2026)

From Liquid to Solid: Formulation and Characterization of Testosterone-Loaded S-SMEDDS Pellets Using a 24 Factorial Design - Ohary de Sousa Borges; Julia Ornelas Kramer; Henrique Pascoa; Yanka Machado de Paula Santos; Leticia Silva Oliveira Freitas; Eliana M. Lima; Luís Antônio Dantas Silva; Danielle Guimarães A. Diniz (AAPS PharmSciTech, 2026)

Differential presence of microplastics in the gastrointestinal tract of tropical fish in relation to trophic levels - Merle M. Borges-Ramírez; Rosa E. Martínez-Cerda; Carlos E. Paz-Ríos; Edgar F. Mendoza-Franco; Atahualpa Sosa-López; Jaime Rendón-von Osten (Regional Studies in Marine Science, 2026)

Mermaids in pools: Ex-situ conservation as a cornerstone for sirenian management worldwide - D.N. Castelblanco-Martínez; E.A. Ramos; A. Alvarez-Aleman; L. von Fersen; R.S. Amaral; F.L.N. Attademo; J.C.G. Borges; L.J. Cabrias-Contreras; D. Caicedo-Herrera; T. Calleson; V.L. Carvalho; A. Dávila-Peñaloza; et al. (Journal for Nature Conservation, 2026)

Temporal trends (1937–2006) in concentrations of toxic elements in neotropical birds from southeastern Mexico - Ruth Partida-Lara; Paula L. Enríquez; José Raúl Vázquez-Pérez; Merle M. Borges-Ramírez; Marina Esperanza Rodríguez-Yah; Jaime Rendón-von Osten (Environmental Monitoring and Assessment, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Beyond the Highlands: Climate Drives Evolutionary Connections Between Ancient Neotropical Mountains and Lowland Biomes - Yago Barros‐Souza; Monique Maianne; Rafael F. Barduzzi; Leonardo M. Borges (Global Ecology and Biogeography, 2026)
Aim The assembly of montane plant communities through time is underlain by historical and abiotic factors. However, the extent of evolutionary connectivity between ancient highland ecosystems and surrounding lowlands remains unclear. Here, we investigate the evolutionary connections between the campos rupestres , a hyperdiverse and fragmented montane vegetation complex in eastern South America, and lowland biomes surrounding it: savannas, rainforests and seasonally dry tropical forests. Location Eastern South America. Time Period Cenozoic. Major Taxa Studied Flowering plants. Methods Using phylogenetic beta diversity analyses for 13 angiosperm clades, we assess the degree of lineage dissimilarity between campos rupestres subregions and adjacent biomes. We also apply generalised dissimilarity modelling to determine the role of climate, soil and geographic distance in shaping spatial patterns of phylogenetic composition. Results Our results reveal high lineage permeability between campos rupestres and surrounding biomes, with lineage sharing largely reflecting biome adjacency. This pattern is mainly driven by shared climatic conditions, which are the strongest predictors of phylogenetic dissimilarity. Main Conclusions We highlight the importance of lineage exchange between lowland and montane environments for the assembly of highland floras. By showing that lineage movements across biome boundaries have been common over time and across spatial scales, our study challenges the idea that ancient Neotropical mountains are isolated sky‐islands. Instead, we emphasise the dynamic nature of montane plant diversity and the pivotal role of climate in shaping evolutionary connections between highlands and lowlands.

Biochemical and physiological characterization of Sp-H, a hyaluronidase isolated from the venom of the scorpionfish Scorpaena plumieri - Milenna M. Pirovani; Helena B. Fiorotti; Juliana S. Cassoli; Jaqueline L. dos Santos; Luciana S. Oliveira; Márcia H. Borges; Juliana B. Coitinho; Fabiana V. Campos; Suely G. Figueiredo (Toxicon, 2026)

Plastic occurrence in Macaronesia: Three years of monitoring on forty-six beaches across nineteen islands in an Atlantic region - Cristopher Domínguez-Hernández; Cristina Villanova-Solano; Soledad Álvarez; Sergio J. Álvarez-Méndez; Adeline Alves; João Canning-Clode; Mara de Castro Abu-Raya; Francisco J. Díaz-Peña; Sofia Garcia; May Gómez; Javier González-Sálamo; Cintia Hernández-Sánchez; et al. (Science of The Total Environment, 2026)

Biomass-derived carbon co-processed in a laboratory-scale coking unit: Detailed chemical evaluation of liquid products and their distillation cuts - Raquel V.S. Silva; Adriana M. Borges; Vanessa O. Nunes; Vinicius B. Pereira; Karen T. Stelzer; Andrea R. Pinho; Débora A. Azevedo (Biomass and Bioenergy, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Electrophysiological modulation of cholinergic neurotransmission by biologically active peptides from Bothrops bilineatus (Viperidae: Crotalinae) venom - Fernanda Y. G. M. Couceiro; Francis L. Pacagnelli; Kristian A. Torres-Bonilla; Stephen Hyslop; Bruno Lomonte; Robert M. Drummond; Daniel C. Pimenta; Rafael J. Borges; Rafael S. Floriano (Archives of Toxicology, 2026)

Tourism education in Europe and the road to Net-Zero: Are universities doing enough? - Anita Conefrey; James Hanrahan; Conor McTiernan; Maria do Rosário Borges; Joana Lima; Jaime Serra; Junwei (Jerry) Yu; María Cristina Barriuso Iglesias; M. Mercedes Galan-Ladero; Martín Gómez-Ullate; Juan-Luis Tato-Jiménez; Alina Badulescu; et al. (Journal of Cleaner Production, 2025)

Chemical and toxicological evaluation of micropollutants degradation in tertiary municipal wastewater by H2O2/UVC - Gabrielly M. Santos; Lucas G. Costa; Eduardo O. Marson; Meliza A.S. Bessa; Raquel W. Becker; Carla F.G. Frois; Carla Sirtori; Adão S. Ferreira; Raquel M.F. Sousa; Waldomiro Borges Neto; Marcelo B. Santos; Solidônio R. Carvalho; et al. (Journal of Environmental Chemical Engineering, 2025)

Exploring the Sleep Quality and Associated Factors Among Truck Drivers in Brazilian Highways: A Cross-Sectional Study - Paulo M. A. Lima; Josiane S. Souza; Ana C. S. Feliciano; Heloísa S. Guerra; Poliana P. Ghazale; Fábio V. A. Borges; Alessandro R. Giovani; Renato C. D. Silva (Sleep and Vigilance, 2025)

Retention of anthropogenic microparticles in a wastewater treatment and reclamation plant combining membrane bioreactor and reverse electrodialysis treatments - Adrián M. Afonso-Álvarez; Sergio J. Álvarez-Méndez; Marina Ugrina; Luisa Vera; Javier Hernández-Borges (Journal of Hazardous Materials, 2025)

Interplay of ant defense and leaf functional traits determine herbivory and fluctuating asymmetry during ontogeny of a myrmecophytic tropical plant - Joan Sebastian Aguilar-Peralta; Marcela Sofía Vaca-Sánchez; Yurixhi Maldonado-López; Mário M. Espírito-Santo; Ken Oyama; Maurício L. Faria; Magno Augusto Zazá Borges; Marcílio Fagundes; G. Wilson Fernandes; Jean Carlos Santos; Pablo Cuevas-Reyes (Flora, 2025)

Ecological risk assessment for metal(oid)s in microplastics and sediments at different depths from cenotes (sinkholes) of Yucatan, Mexico - Jaime Rendón-von Osten; Erick Sosa-Rodríguez; Merle M. Borges-Ramírez (Environmental Research, 2025)

Hippocampal Interneurons Shape Spatial Coding Alterations in Neurological Disorders - Juliane Midori Ikebara; Renata Silva Jorge; Luciana Simões Rafagnin Marinho; Guilherme Shigueto Vilar Higa; Avishek Adhikari; Fernando M. C. V. Reis; Fernando S. Borges; Henning Ulrich; Silvia Honda Takada; Roberto De Pasquale; Alexandre Hiroaki Kihara (Molecular Neurobiology, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Heavy metals and As in feathers of the American kestrel (Falco sparverius) in an arid agriculture landscape on the Baja California peninsula - Martín G. Frixione; Christian Salvadeo; Georgina Brabata-Domínguez; Merle M. Borges-Ramírez; David González-Rivas; Jaime Rendon von Osten (Science of The Total Environment, 2025)

Season and temperature-humidity index affect sperm quality and in vivo fertility of beef bulls - Larysse A. Alves; Reinaldo F. Cooke; Marcelo Sant’Ana Borges; Fabiana F. Souza; John P. Kastelic; André M. Crespilho (Journal of Thermal Biology, 2025)

Pathological findings in free-ranging Didelphis spp. From urban areas in Brazil: A one health perspective - E. Ferreira Machado; M. Lima Borges; J. Garcia; M. Albuquerque Landi; J. Carvalho; J. Fernandes Takahashi; I. Jesus; B. Bernardes da Silva; C. Castagna; C. Lima; T. Zwarg; T. Sanches; et al. (Journal of Comparative Pathology, 2025)

Distribution, composition, and drivers of suspended particulate organic matter in the Gerlache Strait, Northern Antarctic Peninsula - Elis Brandão Rocha; Eunice da Costa Machado; Maurício Garcia de Camargo; Carlos Eduardo de Rezende; Pedro Vianna Gatts; Carlos Rafael Borges Mendes; Raul Rodrigo Costa; Mônica Wallner-Kersanach; Mauricio M. Mata; Rodrigo Kerr (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Gene-Specific Substitution Rates for the Vespertilionidae (Chiroptera: Mammalia) Mitochondrial Genome, with the Description of Three new Mitogenomes - M. S. Borges; M. M. A. Salles; E. F. Oliveira; F. M. Magalhães; D. C. Silva; H. F. M. Oliveira; K. C. Faria; V. N. Laine; T. M. Lilley; J. M. Silva; F. M. C. B. Domingos (Journal of Molecular Evolution, 2025)

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Removing pollutants and recovering resources in treatment wetlands cultivated with ora-pro-nobis and citronella - L. S. Lopes; T. S. Alves; A. M. Araújo; F. F. Cunha; A. P. Rosa; A. C. Borges (International Journal of Environmental Science and Technology, 2025)

Measuring the natural capital of Amazonian forests: A case study of the National Forest of Carajás, Brazil - Tereza Cristina Giannini; Caroline Oliveira Andrino; Rafael Gomes Barbosa-Silva; José A. Bitencourt; Rafael C. Borges; Renata R. Brito; Rosane Cavalcante; Claudia P.W. Costa; Sidnei Dantas; Markus Gastauer; Vitor F. Gomes; Ulysses M. Maia; et al. (Ecosystem Services, 2025)

Chloroplast-based molecular markers for discrimination of economically important Vaccinium species - Maura Flynn Gallagher; Felix E. Enciso-Rodriguez; Edson Mario de Andrade Silva; Annette M. Fahrenkrog; Juan Zalapa; Juliana Benevenuto; Karina Lima Reis Borges; Patricio Munoz (Genetic Resources and Crop Evolution, 2025)

Projecting climate change impacts on the distribution of the most captured tuna species on Atlantic waters - Priscila M. Silva; Francisco O. Borges; Cristina Pita; José Lino Costa; Célia M. Teixeira (Biodiversity and Conservation, 2025)
Tunas are among the most valuable marine resources and some of the most popular seafood worldwide, traded on a global scale. Not only do they support the livelihoods of fishers, they also play a crucial ecological role as both predators and prey. The challenges already faced by fisheries governance in managing these highly migratory species are likely to intensify due to climate-induced changes. This study investigates potential shifts in habitat suitability and geographical distribution of the most captured tuna species in the Atlantic Ocean by 2030 and 2050, across three Shared Socioeconomic Pathway (SSP) scenarios (i.e., SSP1-2.6, 4–6.0, and 5-8.5; CMIP6) using species distribution models (SDM) through MaxEnt. Its findings indicate the start of a potential poleward shift in tuna distribution as early as 2030, accompanied by significant declines in habitat suitability at lower latitudes. This trend poses a risk of range restriction or even local extinction of this group in equatorial regions. Given the socioeconomic importance of tuna species, predicting their responses to climate change could inform effective management strategies ensuring not only the sustainability of tuna populations but also the livelihoods of the communities that depend on them. Future research should incorporate the potential impact of changing environmental conditions on fishing intensity, as this will further shape the long-term distribution of these species.

Advances in Legume Systematics 15: Integrating knowledge on the legume family - Leonardo M. Borges; Marcelo F. Simon; Tânia M. Moura; Luciano P. Queiroz; Marianne Le Roux (Brazilian Journal of Botany, 2025)

Many ways for sensory systems to stumble and fail in the Anthropocene - Renee M. Borges (Journal of Biosciences, 2025)

Methodology for optimizing electrical grounding grids in stratified soils using advanced calculation techniques and evolutionary algorithms - Carlos Leandro Borges da Silva; Thyago Gumeratto Pires; Antonio Marcelino Silva Filho; Junio Santos Bulhões; Orlando M. Oliveira Belo; Clóves Gonçalves Rodrigues; Antonio Paulo Coimbra; Wesley Pacheco Calixto (Swarm and Evolutionary Computation, 2025)

Enhanced UVC treatment for removal of micropollutants using a combination of the oxidants H2O2 and S2O82– - Lucas G. Costa; Eduardo O. Marson; Gabrielly M. Santos; Waldomiro Borges Neto; Solidônio R. Carvalho; Alam G. Trovó (Journal of Environmental Chemical Engineering, 2025)

Unveiling microplastic and metal pollution in giant armadillos (Priodontes maximus) from areas impacted by human activities in the Rio Doce Basin, Brazil - Lucas Gonçalves Queiroz; Lucas M. Barreto; João Manoel de Lima Júnior; Guilherme Maricato; Cassiana Seimi Nomura; Marcelo Pompêo; Rômulo Augusto Ando; Arnaud L.J. Desbiez; Bárbara Rani-Borges (Environmental Research, 2025)

Editorial overview: Parasitoid biology in the Anthropocene: it is getting harder to make a living from parasitism - Renee M Borges; Radhika Venkatesan; Saskya van Nouhuys (Current Opinion in Insect Science, 2025)

Integrating local ecological knowledge into systematic conservation planning for seahorse conservation - Anna Karolina Martins Borges; Vanessa M. Adams; Rômulo Romeu Nóbrega Alves; Tacyana Pereira Ribeiro Oliveira (Conservation Biology, 2025)
Successful long‐term conservation relies on strategic planning for pragmatic actions to mitigate threats. Prioritizing actions and areas to support conservation goals in the most cost‐effective scenario becomes crucial in resource‐limited environments. However, planning and management can be challenging in data‐limited contexts. Incorporating local ecological knowledge (LEK) into conservation planning is an underexplored method of addressing these knowledge gaps. We utilized systematic conservation planning to identify key sites for seahorse threat management in a complex social‐ecological system in a protected area. Through participatory mapping and interviews with artisanal fishers, we gathered insights about seahorses, threats to them, and their socioeconomic significance for the local community. We compared LEK‐derived seahorse conservation priorities with spatial priorities identified using Marxan and with LEK‐derived and science‐derived data to explore LEK's contribution to spatial planning for a data‐poor species and to explore different seahorse threat management scenarios. The LEK‐derived and science‐derived seahorse abundance Marxan scenarios had a strong spatial agreement, emphasizing LEK's role in conservation planning. Furthermore, LEK‐derived data filled key data gaps on the distribution and nature of water‐based threats. Threat management scenarios for land and water‐based threat management had distinct spatial patterns. Incorporating LEK into decision‐making empowered local communities and thus fostered community‐based management. These findings offer insights into conservation planning in data‐deficient scenarios and can aid decision makers and local stakeholders in inclusive conservation strategies. Our results identified priorities for seahorse conservation in the Rio Formoso Estuary and our methods offer a transferable approach for participatory and interdisciplinary planning, which are essential for biodiversity conservation and livelihoods maintenance.

Impact of mangrove restoration on microplastic bioaccumulation in fiddler crabs across degraded, restored, and natural ecosystems - Mariana V. Capparelli; Dulce J. Gámez-Herrera; Rosela Pérez-Ceballos; Nancy Yolimar Suárez-Mozo; Shirley V.D. Fonseca-Peña; Merle M. Borges-Ramírez; Jaime Rendón-von Osten; Arturo Zaldívar-Jiménez; Gabriel M. Moulatlet (Marine Pollution Bulletin, 2025)

Multi-Step Forecasting of Meteorological Time Series Using CNN-LSTM with Decomposition Methods - Eluã Ramos Coutinho; Jonni G. F. Madeira; Dérick G. F. Borges; Marcus V. Springer; Elizabeth M. de Oliveira; Alvaro L. G. A. Coutinho (Water Resources Management, 2025)

Why does community ecology need chemistry? Because keystone molecules can govern food webs - Renee M Borges (Journal of Biosciences, 2025)

Primary intracranial squamous cell carcinoma in a mule - João R.C. Brito Junior; Yanca G.S. Soares; Laynaslan A. Soares; Ismael L. Borges; Rodrigo C. Alves; Daniel M. Assis; Glaucia D. Kommers; Antonio F.M. Dantas; Glauco J.N. Galiza (Journal of Comparative Pathology, 2025)

Historical (1960 – 2011) and spatial analysis of mercury and arsenic in two species of tropical birds in southeastern Mexico - Ruth Partida-Lara; Paula L. Enríquez; José Raúl Vázquez-Pérez; Merle M. Borges-Ramírez; Marina E. Rodríguez-Yah; Jaime Rendón-von Osten (Journal of Hazardous Materials, 2025)

Glyphosate and AMPA in Groundwater, Surface Water, and Soils Related To Different Types of Crops in Mexico - Jaime Rendón-von Osten; Merle M. Borges-Ramírez; Norma G. Ruiz-Velazco; Emmanuel Helguera; Omar Arellano-Aguilar; Alejandro A. Peregrina-Lucano; Felipe Lozano-Kasten (Bulletin of Environmental Contamination and Toxicology, 2025)

Damage and economic impact of wood-borers (Bivalvia, Teredinidae) on artisanal fishing in Morocco: a case study - JAZILA EL JAMAAI; AHMED TAHERI; BILAL EL AJJOURI; MOHAMMED SAID ADLAN MERINI; LUÍSA M. S. BORGES (Mediterranean Marine Science, 2025)
This study presents the first comprehensive assessment of the economic impact of wood-boring bivalves from the family Teredinidae on artisanal fishing in Tangier, Morocco, following the establishment of a new fishing port that has seen a marked increase in infestations since its opening in 2018. We conducted a questionnaire survey with over 40 artisanal shipowners to evaluate the extent of damage and repair costs associated with teredinids. The results indicated that 77.5% of the fleet was affected, with a significant proportion reporting moderate damage. Analysis of wood samples revealed two dominant teredinid species: Lyrodus cf. pedicellatus, and Teredo bartschi, both recorded for the first time in Morocco, marking them as alien invasive species in the region. The vulnerability of wooden boats, particularly those constructed from softwoods (e.g., Picea sp. and Pinus sp.), was evident, while polyester boats remained unaffected. Annual repair costs due to shipworm damage were estimated to exceed Moroccan Dirham (MAD) 4.7 million (US$ 470,000), representing over 6% of the artisanal fishery annual value, significantly impacting the livelihoods of artisanal fishermen. Shipping activities through the Strait of Gibraltar likely facilitated the introduction of teredinids. Their adaptability and rising sea temperatures suggest teredinids’ range will continue to expand, threatening local fishing infrastructure. The findings underscore the urgent need for targeted management strategies to mitigate the economic and ecological impacts of these invasive species on artisanal fishing communities.

A new early diverging lepisosteid fish (Lepisosteiformes) from the Late Cretaceous of southeastern Brazil - Agustín G. Martinelli; Thiago da Silva Marinho; Karen M. Panzeri; Sergio Bogan; Fabiano V. Iori; João de Magalhães Lopes; Francisco Macedo Neto; Pedro H. Fonseca; Giorgio Basilici; Nahuel Vega; Luiz Carlos Borges Ribeiro (Journal of South American Earth Sciences, 2025)

Shared Pheromone Compounds in Neotropical Rice Stink Bugs: The Role of Zingiberenol and Sesquipiperitol - M. C. Blassioli-Moraes; A. Khrimian; M. F. F. Michereff; D. M. Magalhães; J. V. M. Costa; E. R. Hickel; J. A. Barrigossi; R. A. Laumann; S. D. Guggilapu; J. Grazia; M. Borges (Journal of Chemical Ecology, 2025)

Host Manipulations Within Mutualisms: Role of Plant Hormones in Selective Resource Allocation - Manasa Kulkarni; Jyothilakshmi Vadassery; Renee M. Borges (Journal of Chemical Ecology, 2025)

Towards the reference ecosystems for quartzitic campo rupestre: Floristic composition and soil relationships - Jéssica Cunha-Blum; Letícia Ramos; Daniel Negreiros; Dario C. Paiva; Vanessa M. Gomes; Leonardo M. Borges; Aristônio M. Teles; G. Wilson Fernandes (Ecological Engineering, 2025)

The effect of age on heart rate variability indices during and following high-intensity continuous exercise in masters and young cyclists - Nattai R. Borges; Peter R. Reaburn; Scott Michael; Thomas M. Doering (European Journal of Applied Physiology, 2025)
This study compared heart rate variability (HRV) parameters of cardiovascular autonomic regulation between well-trained masters and young cyclists at rest, during and following a continuous cycle (CTS) protocol. Ten masters (age = 56 ± 5 years) and eight young (age = 26 ± 3 years) cyclists completed a 100 min experimental protocol consisting of a 60 min CTS cycling bout at 95% of Ventilatory Threshold 2 followed by 40 min of supine recovery. Beat-to-beat heart rate was measured continuously, and HRV parameters analysed at standardised 5 min intervals during rest, exercise and recovery. The root mean square of the successive differences (RMSSD), low-frequency power and high-frequency power parameters were corrected by division of the R-R interval (time domain), or R-R interval squared (frequency domain). Further, the RMSSD and RMSSD:RR for successive 60-s R-R intervals at the onset (0–10 min) and offset (60–70 min) of CTS exercise were analysed over 10-min periods. The natural logarithm (Ln) of skewed parameters was taken for analysis. Significant interaction effects ( P < 0.05) for 5 min segments were found for (LnRMSSD, LnRMSSD:RR, LnHF and LnHF:RR 2 . Masters cyclists demonstrated lower values of parasympathetic activity at rest and during recovery (15–20 min and 35–40 min) compared to younger cyclists. However, similar HRV responses were observed during exercise, including throughout the acute onset and offset periods ( P > 0.05). This data shows that cardiac autonomic regulation during, or immediately following CTS exercise may not be influenced by age, but masters athletes may exhibit a lower baseline for parasympathetic activity.

Effects of environmental temperature and humidity on sperm quality of bulls of different ages - L.A. Alves; R.F. Cooke; Y.E. Hayek-Martins; F.F. Souza; M. Sant’Ana-Borges; L.F. Canela Souza; N.S. Gonçalves; A.M. Crespilho (Animal Reproduction Science, 2025)

Pollen evolution in the Stryphnodendron clade (Leguminosae, Mimoseae) - Rafael F. Barduzzi; Yago Barros-Souza; Stefany Liau-Kang; Leonardo M. Borges (Brazilian Journal of Botany, 2024)

Stability of milk proteins subjected to UHT treatments: challenges and future perspectives - Alisson Borges de Souza; Rodrigo Stephani; Guilherme M. Tavares (Critical Reviews in Food Science and Nutrition, 2024)

Convergent evolution: What do cats, catnip, aphids, and mosquitoes have in common? - Renee M. Borges (Journal of Biosciences, 2024)

On the effect of two-direction seasonal flows on barchans and the origin of occluded dunes - Willian R. Assis; Danilo S. Borges; Erick M. Franklin (Geomorphology, 2024)

Mixing oat proteins with lentil or faba bean proteins: How is the techno-functional behavior of the different protein systems affected by heat treatments? - Anne Caroline A. Sales; Renato Ishige Borges de Oliveira; Guilherme M. Tavares (Food Hydrocolloids, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Depth estimation of pre-Kalahari basement in Southern Angola using seismic noise measurements and drill-hole data - J. Carvalho; D. Alves; J. Borges; B. Caldeira; D. Cordeiro; A. Machadinho; A. Oliveira; E.C. Ramalho; J.F. Rodrigues; J.M. Llorente; M. Ditutala; J.L. García-Lobón; et al. (Journal of Applied Geophysics, 2024)

Plant defence mechanism in honeydew-mediated plant-Hemiptera-ant interactions and ecosystem sustainability: a review - Rudra Prasad Banerjee; Saroj K. Barik; Renee M. Borges; Madhoolika Agrawal (Environmental Sustainability, 2024)

Oviposition decisions under environment-induced physiological stress in parasitoids - Pratibha Yadav; Renee M Borges (Current Opinion in Insect Science, 2024)

Eight weeks of high-intensity interval training versus stretching do not change the psychoneuroendocrine response to a social stress test in emotionally impulsive humans - F. Javelle; W. Bloch; U. Borges; T. Burberg; B. Collins; N. Gunasekara; T. J. Hosang; T. Jacobsen; S. Laborde; A. Löw; A. Schenk; M. L. Schlagheck; et al. (European Journal of Applied Physiology, 2024)
Purpose Research supports physical activity as a method to heighten stress resistance and resilience through positive metabolic alterations mostly affecting the neuroendocrine system. High-intensity interval training (HIIT) has been proposed as a highly effective time-saving method to induce those changes. However, existing literature relies heavily on cross-sectional analyses, with few randomised controlled trials highlighting the necessity for more exercise interventions. Thus, this study aims to investigate the effects of HIIT versus an active control group on the stress response to an acute psychosocial stressor in emotionally impulsive humans (suggested as being strong stress responders). Methods The study protocol was registered online (DRKS00016589) before data collection. Sedentary, emotionally impulsive adults (30.69 ± 8.20 y) were recruited for a supervised intervention of 8 weeks and randomly allocated to either a HIIT ( n = 25) or a stretching group ( n = 19, acting as active controls). Participants were submitted to a test battery, including saliva samples, questionnaires (self-efficacy- and perceived stress-related), visual analogue scales (physical exercise- and stress-related), and resting electroencephalography and electrocardiography assessing their reaction to an acute psychological stressor (Trier Social Stress Test) before and after the exercise intervention. Results HIIT increased aerobic fitness in all participants, whereas stretching did not. Participants from the HIIT group reported perceiving exercising more intensively than those from the active control group ( ƞ p 2 = 0.108, p = 0.038). No further group differences were detected. Both interventions largely increased levels of joy post-TSST ( ƞ p 2 = 0.209, p = 0.003) whilst decreasing tension ( ƞ p 2 = 0.262, p < 0.001) and worries ( ƞ p 2 = 0.113, p = 0.037). Finally, both interventions largely increased perceived levels of general self-efficacy ( ƞ p 2 = 0.120, p = 0.029). Conclusion This study suggests that 8 weeks of HIIT does not change the psychoneuroendocrine response to an acute psychological stress test compared to an active control group in emotionally impulsive humans. Further replications of supervised exercise studies highly powered with active and passive controls are warranted.

Science for the people, of the people and by the people: The potential of citizen science - Renee M Borges (Journal of Biosciences, 2024)

Inter-annual variation in the microplastics abundance in feces of the Baird's tapir (Tapirus bairdii) from the Selva Maya, México - Jonathan Pérez-Flores; Merle M. Borges-Ramírez; Jorge A. Vargas-Contreras; Jaime Rendón-von Osten (Science of The Total Environment, 2024)

Photodynamic activation of phytochemical-antibiotic combinations for combatting Staphylococcus aureus from acute wound infections - Ariana S.C. Gonçalves; Miguel M. Leitão; José R. Fernandes; Maria José Saavedra; Cristiana Pereira; Manuel Simões; Anabela Borges (Journal of Photochemistry and Photobiology B: Biology, 2024)

Anthropogenic particles determination in northern krill (Meganyctiphanes norvegica) from the Azores region: A keystone species for marine food webs - Cristina Villanova-Solano; João M. Pereira; Cintia Hernández-Sánchez; Javier Hernández-Borges; Christopher K. Pham (Journal of Hazardous Materials, 2024)

Efficient oxidation attenuates porewater‐derived methane fluxes in mangrove waters - Yvonne Y. Y. Yau; Alex Cabral; Gloria Reithmaier; Luiz C. Cotovicz; João Barreira; Gwenaël Abril; Cedric Morana; Alberto V. Borges; Wilson Machado; José M. Godoy; Stefano Bonaglia; Isaac R. Santos (Limnology and Oceanography, 2024)
Mangroves store significant amounts of carbon in both sediment and water. Methane (CH 4 ) is often produced in anoxic, organic‐rich sediments during carbon degradation and released to overlying waters via porewater exchange. Yet, a portion of CH 4 can be oxidized to CO 2 before emission. Here, we investigate whether CH 4 oxidation impacts its emissions using high‐temporal resolution CH 4 concentration and stable isotope (δ 13 C‐CH 4 ) observations collected over 14 tidal cycles in 2 Brazilian mangrove creeks with no river inputs. We found higher CH 4 concentrations (~ 150 nM) more depleted in 13 C (−75‰) during low tide than high tide at both creeks. Similar δ 13 C‐CH 4 values between low tide surface waters and porewaters further suggest tidally driven porewater exchange as the main source of CH 4 . More 13 C‐enriched CH 4 in surface waters and surface sediments than deep sediments indicate partial CH 4 oxidation prior to exchange with the atmosphere. A stable isotope mass balance revealed that 17–58% of CH 4 was oxidized at rates of 3–25 μ mol m −2 d −1 in the water column of tidal creeks. A larger portion of deep porewater CH 4 (45–61%) was oxidized in sediments prior to porewater exchange with surface creek waters. The two mangrove creeks had average water–air CH 4 fluxes of 51–109 μ mol m −2 d −1 over spring‐neap tidal cycles. These aquatic CH 4 emissions offset only 4 oxidation in both surface water and sediment attenuated CH 4 emissions to the atmosphere.

Mouthing plenitudes: Of famines, leghemoglobin, vertical farming, and future foods - Renee M Borges (Journal of Biosciences, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Sexual system variation in legumes (Leguminosae): underpinning genomic study with new tools to describe inflorescence morphology - Quentin Cronk; Leonardo M. Borges (Brazilian Journal of Botany, 2024)

Bacterial septicemia and herpesvirus infection in Antarctic fur seals (Arctocephalus gazella) stranded in the São Paulo coast, Brazil - Aricia Duarte-Benvenuto; A. M. Sánchez-Sarmiento; A. C. Ewbank; R. Zamana-Ramblas; S. Costa-Silva; N. Silvestre; T. Faita; L. B. Keid; R. M. Soares; C. F. Pessi; J. R. Sabbadini; M. F. Borges; et al. (Veterinary Research Communications, 2024)
In August 2021, two juvenile male Antarctic fur seals ( Arctocephalus gazella ) stranded in the southeastern Brazilian coast and were referred to rehabilitation centers. The animals presented increased body temperature, prostration, respiratory distress and despite treatment died. A necropsy following a standardized protocol was performed, and formalin-fixed tissues were processed for microscopic examination. Samples were screened for morbillivirus, herpesvirus, and Brucella spp. by molecular analyses (PCR, RT-PCR). Bacteriological culture was performed in samples collected from the lungs, trachea, and lymph nodes of both cases. The main histopathologic findings were of infectious nature, including multifocal necrotizing and fibrinous mixed interstitial pneumonia, bronchiolitis, and bronchitis, with intralesional myriad bacteria associated with vascular fibrinoid necrosis. Pseudomonas aeruginosa was isolated from tracheal and lung swabs of Case 1, and Klebsiella oxytoca was found in nostril swabs, tracheobronchial lymph nodes, and lung of Case 2. Gammaherpesvirus infection was detected in both cases, and the sequences retrieved were classified into the genus Percavirus . All tested samples were PCR-negative for Brucella spp. and morbillivirus. We hypothesize that the deficient immunological status in association with starvation predisposed the reactivation of herpesvirus and secondary bacterial co-infections. To the authors’ knowledge, this is the first molecular detection of herpesvirus in an Antarctic pinniped. These findings reinforce that Otariid gammaherpesvirus circulating in the Southern Hemisphere are likely endemic in the Arctocephalus genus. This report contributes to the current knowledge of health aspects affecting wild pinnipeds, especially in the poorly studied Antarctic species.

Recent advances in nanomaterial-based optical biosensors for food safety applications: Ochratoxin-A detection, as case study - Diana I. Meira; Ana I. Barbosa; Joel Borges; Rui L. Reis; Vitor M. Correlo; Filipe Vaz (Critical Reviews in Food Science and Nutrition, 2024)

Early induction of luteolysis in a timed AI protocol increases reproductive performance in beef cows - Eduardo P. Silva; Alfredo Q. Antoniazzi; João B.S. Borges; Pedro L.J. Monteiro; Amanda B. Machado; Marcelo M. Dias; Valério V.M. Portela Junior; Milo C. Wiltbank (Domestic Animal Endocrinology, 2024)

Highly conserved and extremely variable: The paradoxical pattern of toxin expression revealed by comparative venom-gland transcriptomics of Phalotris (Serpentes: Dipsadidae) - Omar M. Entiauspe-Neto; Pedro G. Nachtigall; Márcio Borges-Martins; Inácio L.M. Junqueira-de-Azevedo; Felipe G. Grazziotin (Toxicon, 2024)

Mass yields of products and composition of syngas from pyrolysis of Brazilian plastic solid wastes: Combustion simulation and burner design to minimize COx and CxHy emissions - José S. Pessoa Filho; Bernardo A.S. Penha; Sarah V. Satto; Euclides A.P. Lima; Valério L. Borges; Valdislaine M. Silva; Marcelo B. Santos; Alam G. Trovó; Solidônio R. Carvalho (Process Safety and Environmental Protection, 2024)

Effect of modified citrus pectin on galectin-3 inhibition in cisplatin-induced cardiac and renal toxicity - Diego D. Santos; Nycole M. Belote; Gisela R.S. Sasso; Rebeca D. Correia-Silva; Paulo C. Franco; Artur Francisco da Silva Neto; Fernanda T. Borges; Lila M. Oyama; Cristiane D. Gil (Toxicology, 2024)

Who holds the reins? Context-dependent resource allocation in the mutualism between fig trees and their fig wasp pollinators - Manasa Kulkarni; Nehal Vijay Naik; Renee M. Borges (Oecologia, 2024)

Larval dynamics suggest phenological strategies and positive effect of marine protected areas controlling indigenous and non-indigenous crab populations - José M. Landeira; Effrosyni Fatira; Jose A. Cuesta; Christoph D. Schubart; Sergio Moreno-Borges; Adriana Rodríguez (Frontiers in Marine Science, 2024)
The early life of most decapod crustaceans takes place in the water column as larvae before they settle in benthic habitats. The spatial and temporal variability in the settling of larval stages offers valuable insights into the potential recruitment of natural populations. To explore this, we studied megalopa assemblages at various segments of coastline on El Hierro and Lanzarote islands, both within and outside the Marine Protected Areas (MPAs) of each island. The study spanned four consecutive oceanographic periods in the Canary Islands (NW Africa), employing light traps for sample collection. The low number of recorded species suggested that light traps exhibit selectivity, particularly for megalopae belonging to Portunidae and Grapsidae. El Hierro, which experienced warmer sea surface temperatures, displayed higher megalopa abundance values than Lanzarote and distinct larval assemblages was observed between these two islands. Similarly, we identified significant variations in abundance and species composition between stratified and mixing seasons. These seasonal differences were influenced by the dominance of Achelous hastatus , Percnon gibessi , and Cronius ruber during the stratified season. In Lanzarote, C. ruber was not recorded during the mixing season, suggesting that the colder conditions there may constrain its reproduction. Interestingly, we observed that species traditionally harvested from the intertidal zone for human consumption ( Plagusia depressa ) or used as bait for recreational fishing ( Pachygrapsus spp. and P. gibessi ) exhibited higher megalopa abundances within the MPAs. In contrast, we noted lower megalopa densities of the non-indigenous species C. ruber within the protected areas. These results indicate a positive effect of MPAs controlling indigenous and non-indigenous crab populations. Moreover, the study provides novel data, showing that light traps are suitable for monitoring the temporal occurrence, abundance, and spatial distribution of non-indigenous and commercially exploited species. This is key for adopting an ecosystem-based approach to manage marine resources.

A One pathology, Multicentre portuguese approach to thyroid tumours of dogs and cats - T.B. Gaspar; I. Borges; S. Canberk; A. Monteiro; J. Catarino; M. Pinto; E. Teixeira; A. Canadas-Sousa; S. Branco; D. Silva; H. Lima de Carvalho; P. Faísca; et al. (Journal of Comparative Pathology, 2024)

A selection process based on the robustness of anti-Listeria monocytogenes activity reveals two strains of Carnobacterium maltaromaticum with biopreservation properties in cheese - Lamia Cherrat; Alexis Dijamentiuk; Sara M. El Kheir; Cécile Mangavel; Annelore Elfassy; Anne-Marie Revol-Junelles; Frédéric Borges (International Journal of Food Microbiology, 2024)

The Brazil current cyclonic meandering and shelf-slope water exchanges at 27°S–31°S - João Pedro M. Amorim; Ilson C.A. da Silveira; Milton Borges-Silva; Pedro W.M. Souza-Neto; Piero S. Bernardo; Marcelo Dottori; Wellington C. Belo; Renato P. Martins; Tiago C. Biló (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Antimicrobial resistance and public and animal health risks associated with pathogenic Escherichia coli isolated from calves - Dircéia Aparecida da Costa Custódio; Carine Rodrigues Pereira; Maysa Serpa Gonçalves; Anna Cecília Trolesi Reis Borges Costa; Pedro Felipe Rodrigues de Oliveira; Bruna Henrique Pinto da Silva; Giovanna Botelho Carneiro; Fernanda Morcatti Coura; Andrey Pereira Lage; Marcos Bryan Heinemann; Geraldo M.árcio da Costa; Elaine Maria Seles Dorneles (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Prior denaturation and aggregation of whey proteins: is this a useful strategy for increasing the content of these proteins in UHT high-protein dairy beverages? - Alisson Borges de Souza; Ana Augusta Odorissi Xavier; Rodrigo Stephani; Guilherme M. Tavares (Food and Bioproducts Processing, 2024)

A carbonate system time series in the Eastern Mediterranean Sea. Two years of high-frequency in-situ observations and remote sensing - C. Frangoulis; N. Stamataki; M. Pettas; S. Michelinakis; A. L. King; L. Giannoudi; K. Tsiaras; S. Christodoulaki; J. Seppälä; M. Thyssen; A.V. Borges; E. Krasakopoulou (Frontiers in Marine Science, 2024)
The rate of ocean uptake of anthropogenic CO 2 has declined over the past decade, so a critical question for science and policy is whether the ocean will continue to act as a sink. Large areas of the ocean remain without observations for carbonate system variables, and oceanic CO 2 observations have declined since 2017. The Mediterranean Sea is one such an area, especially its eastern part, where there is a paucity of carbonate system data, with large areas not sampled or only sampled by ship-based discrete measurements as opposed to high frequency, sensor-equipped time-series fixed stations. The aim of this study was to analyze a multi-year time-series of high-frequency (hourly) partial pressure CO 2 (pCO 2 ) and pH measurements in the Eastern Mediterranean, along with low-frequency (monthly) measurements of total dissolved inorganic carbon and total alkalinity. The pCO 2 time-series was the first obtained in the Eastern Mediterranean. The study was conducted at a fixed platform of the POSEIDON system (Heraklion Coastal Buoy) located near Crete Island. Temperature was the dominant factor controlling the temporal variability of pCO 2 and pH, while the remaining non-thermal variability appeared to be related to evaporation, water mixing, and biological remineralization-production. The air-sea CO 2 fluxes indicated a transition from a winter-spring sink period to a summer-autumn source period. The annual air-sea CO 2 flux was too low (-0.16 ± 0.02 mol m -2 yr -1 ) and variable to conclusively characterize the area as a net source or sink of CO 2 , highlighting the need for additional high frequency observation sites. Algorithms were developed using temperature, chlorophyll and salinity data to estimate pCO 2 and total alkalinity, in an effort to provide tools for estimates in poorly observed areas/periods from remotely sensed products. The applicability of the algorithms was tested using Surface Ocean CO 2 Atlas (SOCAT) data from the Eastern Mediterranean Sea (1999 to 2020) which showed that the algorithm pCO 2 estimates were generally within ±20 μatm of the pCO 2 values reported by SOCAT. Finally, the integration and analysis of the data provided directions on how to optimize the observing strategy, by readapting sensor location and using estimation algorithms with remote sensing data.

Carcass traits and meat quality of lambs fed with rehydrated ground corn silage - Leandro A.S. Silva; Cláudia L.S. Lima; Douglas dos S. Pina; Henry D.R. Alba; Maria L.G.M.L. de Araújo; Luís G.A. Cirne; José A.G. Azevêdo; Carlindo S. Rodrigues; Larissa M. Borges; Maria L.O. Chaves; Gleidson G.P. de Carvalho (Small Ruminant Research, 2024)

Synergistic effects of microplastic and lead trigger physiological and biochemical impairment in a mangrove crab - Mariana V. Capparelli; Ricardo Dzul-Caamal; Erick M. Rodríguez-Cab; Merle M. Borges-Ramírez; Jaime Rendón-von Osten; Karen Beltran; Brian Pichardo-Casales; Alethia I. Ramírez-Olivares; Jorge Arturo Vargas-Abúndez; Carl L. Thurman; Gabriel M. Moulatlet; Carlos Rosas (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Dose–Response Effect of Saccharomyces cerevisiae UFMG A-905 on the Prevention of Asthma in an Animal Model - Thamires M. S. Milani; Camila M. Sandy; Ana Paula Carvalho Thiers Calazans; Rosana Q. Silva; Vanessa M. B. Fonseca; Flaviano S. Martins; Marcos C. Borges (Probiotics and Antimicrobial Proteins, 2024)

Boil-off recovery system for natural gas stations: an approach to increase energy efficiency and reduce greenhouse gases - A. D. S. Borges; M. Oliveira; B. Varandas (International Journal of Environmental Science and Technology, 2024)
Improving the efficiency of energy use is of utmost importance in the context of climate change. Indeed, greater efficiency in the end-use of energy will make a significant contribution to lowering primary energy consumption and reducing CO 2 and other greenhouse gas emissions. This paper presents an approach that enables a compact liquefied natural gas station to operate without being connected to the public electric grid. It is achieved by using the Boil-off gas generated by the vehicle supply process and feeding it to a generator which, together with a photovoltaic (PV) system, can produce electrical energy. Results from a year of trial operations at the station in Escariz, Portugal, demonstrate that it is possible to recover an average of 8.66 kg of Boil-off gas daily while generating a 345% excess of electrical energy when combined with the PV system, enabling the station to be self-sustainable in terms of electricity. Based on the experimental data and calculation methodology, the project was able to earn an estimated monthly revenue of €176.27 throughout the study period while also preventing the emission of 8549 kg of CO 2 equivalent from natural gas combustion in vehicles.

Food for healthier aging: power on your plate - Denise Mafra; Stephanie Ariemu Ugochukwu; Natalia A Borges; Ludmila F. M. F Cardozo; Peter Stenvinkel; Paul G. Shiels (Critical Reviews in Food Science and Nutrition, 2024)

Solastalgia, our deteriorating environment, and Spirit of Place - Renee M Borges (Journal of Biosciences, 2024)

Functional leaf-trait variability and herbivory in oaks along a Mexican avocado agrosystem mosaic - Marcela Sofía Vaca-Sánchez; Mário M. Espírito-Santo; Yurixhi Maldonado-López; Ken Oyama; Abel Pérez-Solache; Maurício Lopes de Faria; Magno Augusto Zazá Borges; G. Wilson Fernandes; Pablo Cuevas-Reyes (Flora, 2024)

Investigating an extreme meteo-oceanographic event in the southern Brazil from in situ observations and modeling results - Dayanis M. Borges; Humberto L. Varona; Marcelo F. Alonso; Moacyr Araujo; Fabrice Hernandez (Regional Studies in Marine Science, 2023)

Fermented food: Should patients with cardiometabolic diseases go back to an early neolithic diet? - D. Mafra; N. A. Borges; L. Alvarenga; M. Ribeiro; L. Fonseca; V. O. Leal; P. G. Shiels; P. Stenvinkel (Critical Reviews in Food Science and Nutrition, 2023)

Three-dimensional evaluation of beaches of oceanic islands as reservoirs of plastic particles in the open ocean - Christopher K. Pham; Sofia G. Estevez; João M. Pereira; Laura Herrera; Yasmina Rodríguez; Cristopher Domínguez-Hernández; Cristina Villanova-Solano; Cintia Hernández-Sánchez; Francisco J. Díaz-Peña; Javier Hernández-Borges (Science of The Total Environment, 2023)

Carbon dioxide and methane capture in metal-organic framework MIL-101(Cr) at high pressure - Tamires R. Menezes; Kátilla M.C. Santos; Thauane S.L. Silva; Klebson S. Santos; André L. Ramos; Gustavo R. Borges; Elton Franceschi; Cláudio Dariva; Juliana F. De Conto; Silvia M. Egues; Cesar C. Santana (Gas Science and Engineering, 2023)

Reverse ethnopharmacological-guided study of Aristolochia trilabiata leaves - unveiling its antioxidant potential and chemical profile - Andrew Magno Teixeira; Paulo Wender P. Gomes; Fabio Araújo da Silva; Paulo Weslem P. Gomes; Michael Murgu; Ricardo M. Borges (South African Journal of Botany, 2023)

Contrasting host use and feeding behavior by sympatric mesograzers - Caio A. Paula; Dalila J. Borges; Aynara R. Andrade; Fosca P. P. Leite; Tânia M. Costa; Glauco B. O. Machado (Marine Ecology, 2023)
Marine mesograzers use macroalgae as food and habitat and may have strong top‐down effects on plants and macroalgae. Sympatric mesograzer species often differ regarding host use and feeding behavior, which may lead to distinct impacts by these consumers on primary producers. The amphipods Hyale niger and Ampithoe marcuzzii are mesograzers abundant that co‐occur in Brazilian waters and, although they use several macroalgae as habitat, it is unknown how much the food value of these hosts explains the host use pattern by the two mesograzers. Herein, we investigated the abundance and feeding behavior of the sympatric amphipods H. niger and A. marcuzzii . For that, their abundance on the macroalgal hosts Sargassum filipendula , Padina gymnospora , and Dichotomaria marginata was evaluated seasonally in a rocky shore at Fortaleza Beach, state of São Paulo, Brazil. Also, multiple‐choice and no‐choice feeding experiments were carried out at laboratory to evaluate the feeding behavior of these mesograzers. The abundance of H. niger was similar among the three macroalgal hosts (except during winter), while A. marcuzzii was more abundant on Dichotomaria and Padina than Sargassum in all seasons. Moreover, H. niger consumed more Padina than Dichotomaria and Sargassum in both feeding experiments. In turn, A. marcuzzii preferred to feed on Padina when it had a choice and consumed the three macroalgal hosts at similar levels in the no‐choice feeding experiment. Overall, H. niger and A. marcuzzii differ from each other regarding their feeding behavior and host use pattern. In particular, the food value of macroalgae seems to partially explain the host use by A. marcuzzi , but not by H. niger . The differences between H. niger and A. marcuzzii may result in varying impacts on primary producers.

Wind and turbulence relationship with NO2 in an urban environment: a fine-scale observational analysis - C. Román-Cascón; C. Yagüe; P. Ortiz-Corral; E. Serrano; B. Sánchez; M. Sastre; G. Maqueda; E. Alonso-Blanco; B. Artiñano; F.J. Gómez-Moreno; E. Diaz-Ramiro; J. Fernández; et al. (Urban Climate, 2023)

P13-12: Heated tobacco and cigarette smoke exposure impairs macrophage responsiveness and functions - P. Scharf; S. Sandri; P.P. Borges; T.F. de Oliveira; M. Aschner; S.H.P. Farsky (Toxicology Letters, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Powdery mildew (Erysiphe cruciferarum) on Brassicaceae in Brazil - Rafaela C. F. Borges; Stéfani dos Santos Leite; João Marcos T. Martins; Maria D. M. Santos; Josiene S. Veloso; Nuno R. Madeira; Maria Esther N. Fonseca; Leonardo S. Boiteux; Ailton Reis (Australasian Plant Pathology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Understanding the chemical language of the natural pharmacopeia: Whose hallucinogen is it anyway? - Renee M. Borges (Journal of Biosciences, 2023)

Assessing water quality of Paraopeba River (Minas Gerais, Brazil) after the rupture of tailings dam - F. V. Fonseca; A. M. F. Linhares; J. R. P. Silva; L. L. S. Silva; I. D. Bassin; J. P. Bassin; F. A. Kronemberger; A. C. Habert; C. P. Borges (International Journal of Environmental Science and Technology, 2023)

Phylogeographic and demographic patterns reveal congruent histories in seven Amazonian White‐Sand ecosystems birds - João Marcos Guimarães Capurucho; Mary V. Ashley; Cintia Cornelius; Sergio H. Borges; Camila C. Ribas; John M. Bates (Journal of Biogeography, 2023)
Aim The drivers of genetic diversity in Amazonia, the most species‐rich set of ecosystems on Earth, are still incompletely understood. Species from distinct Amazonian ecosystems have unique biogeographic histories that will reflect regional landscape and climatic drivers of genetic diversity. We studied bird species from patchy Amazonian white‐sand ecosystems (WSE) to evaluate the occurrence of shared biogeographic patterns to better understand the complex environmental and landscape history of Amazonia and its biodiversity. Location Northern South America; Amazonia. Taxon Passeriformes. Methods We sequenced Ultra‐conserved Elements (UCEs) from 177 samples of seven bird species associated with WSE that have overlapping ranges. We used the SNP matrices and sequence data to estimate genetic structure and migration surfaces using ‘conStruct’ and eems , performed model‐selection to obtain the most probable demographic histories on ‘PipeMaster ’ and implemented analyses of shared demography with ecoevolity . Results Shallow genetic structure patterns varied among species. The Amazon river was the only barrier shared among them. Population structure dates to no more than 450,000 years ago. Nine geographically structured populations showed signals of population size changes and eight of these occur in Northern Amazonia. Population expansion was inferred at two distinct times: ~100,000 and ~ 50,000 years ago. The timing of co‐expanding populations is consistent with differences in habitat preference, as species that prefer dense scrubby to forested vegetation expanded more recently compared to species that prefer open vegetation. Main conclusions WSE species responded in concert to environmental and landscape changes that occurred in the relatively recent past. Population expansions were likely driven by the genesis of new WSE patches and a return to wetter conditions after glacial periods. Pleistocene climatic cycles affected the distribution and dynamics of open vegetation habitats in Amazonia, especially in the Northern region, driving genetic diversity and demographic patterns of its associated biota.

Environmental risk of microplastics in a Mexican coastal lagoon ecosystem: Anthropogenic inputs and its possible human food risk - Omar Celis-Hernandez; Enrique Ávila; Jaime Rendón-von Osten; E. Antony Briceño-Vera; M. Merle Borges-Ramírez; A. Mario Gómez-Ponce; V. Mariana Capparelli (Science of The Total Environment, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

A global analysis of avian island diversity–area relationships in the Anthropocene - Thomas J. Matthews; Joseph P. Wayman; Robert J. Whittaker; Pedro Cardoso; Julian P. Hume; Ferran Sayol; Konstantinos Proios; Thomas E. Martin; Benjamin Baiser; Paulo A. V. Borges; Yasuhiro Kubota; Luiz dos Anjos; et al. (Ecology Letters, 2023)
Research on island species–area relationships (ISAR) has expanded to incorporate functional (IFDAR) and phylogenetic (IPDAR) diversity. However, relative to the ISAR, we know little about IFDARs and IPDARs, and lack synthetic global analyses of variation in form of these three categories of island diversity–area relationship (IDAR). Here, we undertake the first comparative evaluation of IDARs at the global scale using 51 avian archipelagic data sets representing true and habitat islands. Using null models, we explore how richness‐corrected functional and phylogenetic diversity scale with island area. We also provide the largest global assessment of the impacts of species introductions and extinctions on the IDAR. Results show that increasing richness with area is the primary driver of the (non‐richness corrected) IPDAR and IFDAR for many data sets. However, for several archipelagos, richness‐corrected functional and phylogenetic diversity changes linearly with island area, suggesting that the dominant community assembly processes shift along the island area gradient. We also find that archipelagos with the steepest ISARs exhibit the biggest differences in slope between IDARs, indicating increased functional and phylogenetic redundancy on larger islands in these archipelagos. In several cases introduced species seem to have ‘re‐calibrated’ the IDARs such that they resemble the historic period prior to recent extinctions.

Microplastics in sediments from the southern Gulf of Mexico: Abundance, distribution, composition, and adhered pollutants - Jaime Rendón-von Osten; Jorge A. Benítez-Torres; R. Isaac Rojas-González; Fernando Morgado; Merle M. Borges-Ramírez (Science of The Total Environment, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

Cryptophytes: An emerging algal group in the rapidly changing Antarctic Peninsula marine environments - Carlos Rafael Borges Mendes; Raul Rodrigo Costa; Afonso Ferreira; Bruno Jesus; Virginia Maria Tavano; Tiago Segabinazzi Dotto; Miguel Costa Leal; Rodrigo Kerr; Carolina Antuarte Islabão; Andréa de Oliveira da Rocha Franco; Mauricio M. Mata; Carlos Alberto Eiras Garcia; et al. (Global Change Biology, 2023)
The western Antarctic Peninsula (WAP) is a climatically sensitive region where foundational changes at the basis of the food web have been recorded; cryptophytes are gradually outgrowing diatoms together with a decreased size spectrum of the phytoplankton community. Based on a 11‐year (2008–2018) in‐situ dataset, we demonstrate a strong coupling between biomass accumulation of cryptophytes, summer upper ocean stability, and the mixed layer depth. Our results shed light on the environmental conditions favoring the cryptophyte success in coastal regions of the WAP, especially during situations of shallower mixed layers associated with lower diatom biomass, which evidences a clear competition or niche segregation between diatoms and cryptophytes. We also unravel the cryptophyte photo‐physiological niche by exploring its capacity to thrive under high light stress normally found in confined stratified upper layers. Such conditions are becoming more frequent in the Antarctic coastal waters and will likely have significant future implications at various levels of the marine food web. The competitive advantage of cryptophytes in environments with significant light level fluctuations was supported by laboratory experiments that revealed a high flexibility of cryptophytes to grow in different light conditions driven by a fast photo‐regulating response. All tested physiological parameters support the hypothesis that cryptophytes are highly flexible regarding their growing light conditions and extremely efficient in rapidly photo‐regulating changes to environmental light levels. This plasticity would give them a competitive advantage in exploiting an ecological niche where light levels fluctuate quickly. These findings provide new insights on niche separation between diatoms and cryptophytes, which is vital for a thorough understanding of the WAP marine ecosystem.

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

A Braver New World? Of chatbots and other cognoscenti - Renee M. Borges (Journal of Biosciences, 2023)

Ovarian aging in humans: potential strategies for extending reproductive lifespan - Marcelo Borges Cavalcante; Olga Goiana Martins Sampaio; Fernanda Eunice Araújo Câmara; Augusto Schneider; Bianca Machado de Ávila; Juliane Prosczek; Michal M. Masternak; Adriana Rolim Campos (GeroScience, 2023)

More than meets no eyes: Taxonomic status of a Liotyphlops (Serpentes: Anomalepididae) blindsnake from the Atlantic Rainforest - Omar M. Entiauspe-Neto; Francisco L. Franco; Claudia Koch; Arthur Tiutenko; Juliana M. Wingert; Márcio Borges-Martins (Zoologischer Anzeiger, 2023)

Antarctica Slope Front bifurcation eddy: A stationary feature influencing CO2 dynamics in the northern Antarctic Peninsula - Brendon Yuri Damini; Raul Rodrigo Costa; Tiago S. Dotto; Carlos Rafael Borges Mendes; Juan Camilo Torres-Lasso; Marina do V.C. Azaneu; Mauricio M. Mata; Rodrigo Kerr (Progress in Oceanography, 2023)

Fast Identification Method for Screening Bacteria from Faecal Samples Using Oxford Nanopore Technologies MinION Sequencing - Ana Sofia G. Borges; Meghna Basu; Erik Brinks; Corinna Bang; Gyu-Sung Cho; John F. Baines; Andre Franke; Charles M. A. P. Franz (Current Microbiology, 2023)
Most bacterial identification methods require extensive culturing, strain purification and DNA extraction protocols. This leads to additional expenses and time lags when isolating specific bacteria from complex microbiological ecosystems. This study aimed to develop a fast and robust method for identification of lactobacilli, bifidobacteria and Bacteroides in human faecal samples. Bacteria from faecal samples were cultured anaerobically on selective media. Sonication-based DNA extraction was performed, followed by almost complete 16S rRNA gene polymerase chain reaction amplification and MinION sequencing with the Flongle adapter. Sequence analysis was performed using NanoCLUST, while RStudio was used for graphics. For 110 of the 125 colonies investigated, 100% of reads were attributed to a single species, while the remaining 15 colonies consisted of mixtures of up to three different species. The proposed bacterial identification method is advantageous for isolating particular bacteria for which there are no exclusively selective media, as it avoids lengthy colony purification and DNA purification methods, and yields a quick colony identification with high accuracy. Therefore, this method can be used for directly screening for pure cultures of target microorganisms and is suitable for the identification of bacteria in culturomics studies.

Sedimentation in UHT high-protein dairy beverages: Influence of sequential preheating coupled with homogenisation or supplementation with carbohydrates - Alisson Borges de Souza; Ana Augusta O. Xavier; Rodrigo Stephani; Guilherme M. Tavares (International Dairy Journal, 2023)

Prediction of permeability of porous media using optimized convolutional neural networks - Eliaquim M. Ramos; Marcio R. Borges; Gilson A. Giraldi; Bruno Schulze; Felipe Bernardo (Computational Geosciences, 2023)

Ultrastructural study of Manihot esculenta amyloplast: intragranular channels and membrane lipid profiling - Osman F. Silva; André L. A. Guimarães; Ricardo M. Borges; Cristina T. Andrade; Veronica Calado (Brazilian Journal of Botany, 2023)

Anti-inflammatory potential of baicalein combined with silk fibroin protein in a zebrafish model (Danio rerio) - Fabrício H. Holanda; Arlefe N. Ribeiro; Brenda L. Sánchez-Ortiz; Gisele C. de Souza; Swanny F. Borges; Adriana M. Ferreira; Alexandro C. Florentino; Sérgio A. Yoshioka; Lienne S. Moraes; José Carlos T. Carvalho; Irlon M. Ferreira (Biotechnology Letters, 2023)

Influence of pigeon pea (Cajanus cajan) on oviposition behaviour of Diceraeus melacanthus stink bug, an important pest of soybean and maize crops in South America - M. Borges; M. F. F. Michereff; R. A. Laumann; G. T. Santana; B. S. Castro; C. C. Silva; M. C. Blassioli-Moraes (Arthropod-Plant Interactions, 2023)

Spatial‐ and lineage‐dependent processes underpin floristic assembly in the megadiverse Eastern South American mountains - Yago Barros‐Souza; Leonardo M. Borges (Journal of Biogeography, 2023)
Aim The astonishing diversity of ancient mountains was likely shaped by multiple evolutionary processes. However, there is an ongoing debate on what were the main processes driving the assembly of campos rupestres , the mega‐diverse flora of Eastern South American mountains. Although the ancient nature of these mountains suggests their flora should be composed by relatively older lineages, they harbour a number of recently diverged clades. To better understand the evolution of ancient mountains' floras, we tested if the campos rupestres are mainly composed by relatively old or recent communities and if angiosperm diversity is geographically structured using analyses of diversity and endemism. Location Eastern South America. Time Period Oligocene/Miocene to the present. Taxon Flowering plants. Methods We used analyses of diversity and endemism for 10% of the campos rupestres flora. We obtained distribution data from online databases, and phylogenetic hypotheses from the literature. With these datasets, we estimated alpha and beta metrics of taxonomic and phylogenetic diversity, and conducted categorical analyses of neo‐ and palaeo‐endemism. Results Phylogenetic overdispersion predominates in the campos rupestres . However, this general pattern is permeated by both lineage‐ and site‐specific phylogenetic clustering, suggesting that recent diversification events depend on particular regional conditions and on the overall maintenance of old lineages. Although endemism patterns vary among different campos rupestres sites, palaeo‐endemism is widespread and particularly prominent where phylogenetic overdispersion is evident. Moreover, while phylogenetic composition indicates variable past spatial connections across different sites, taxonomic composition is highly geographically structured and seems to be influenced by the vegetation surrounding the campos rupestres and/or by abiotic conditions. Main Conclusions Our results reinforce the idiosyncratic nature of diversification patterns in ancient mountains and suggest that old, climatically buffered, infertile montane ecosystems not only include both relatively old and recent lineages, but that recent diversification is lineage‐ and spatially‐dependent.

A roadmap for ladybird conservation and recovery - António O. Soares; Danny Haelewaters; Olga M. C. C. Ameixa; Isabel Borges; Peter M. J. Brown; Pedro Cardoso; Michiel D. de Groot; Edward W. Evans; Audrey A. Grez; Axel Hochkirch; Milada Holecová; Alois Honěk; et al. (Conservation Biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.

High-throughput phenotyping by deep learning to include body shape in the breeding program of pacu (Piaractus mesopotamicus) - Milena V. Freitas; Celma G. Lemos; Raquel B. Ariede; John F.G. Agudelo; Rubens R.O. Neto; Carolina H.S. Borges; Vito A. Mastrochirico-Filho; Fábio Porto-Foresti; Rogério L. Iope; Fabrício M. Batista; José R.F. Brega; Diogo T. Hashimoto (Aquaculture, 2023)

Increased oyster aquaculture in the Sado Estuary (Portugal): How to ensure ecosystem sustainability? - Ana C. Brito; Humberto Pereira; Ana Picado; Joana Cruz; Rui Cereja; Beatriz Biguino; Paula Chainho; Ângela Nascimento; Frederico Carvalho; Sara Cabral; Cátia Santos; Carla Palma; et al. (Science of The Total Environment, 2023)

Cellular Aging Secretes: a Comparison of Bone-Marrow-Derived and Induced Mesenchymal Stem Cells and Their Secretome Over Long-Term Culture - Ana Marote; Diogo Santos; Bárbara Mendes-Pinheiro; Cláudia Serre-Miranda; Sandra I. Anjo; Joana Vieira; Filipa Ferreira-Antunes; Joana Sofia Correia; Caroline Borges-Pereira; Andreia G. Pinho; Jonas Campos; Bruno Manadas; et al. (Stem Cell Reviews and Reports, 2023)

Identification of genes associated with environmental persistence in Campylobacter jejuni and Campylobacter coli isolates from processing in a broiler abattoir - A. Carbonero; A. Maldonado-Iniesta; Y. Trujillo; J. Perea; M. Riofrío; I. Garcia-Bocanegra; C. Borge (Veterinary Research Communications, 2022)
The aim of this study was to determine the prevalence of the htr A, htr B and ppk 1 genes -all of which are related to environmental persistence- in C. jejuni and C. coli isolates obtained from abattoir samples at the arrival of broilers (initial stage) and in meat products after processing (final stage). A total of 119 DNA extracts (55 C. jejuni and 64 C. coli ) were included in the study . Identification of genes was performed by conventional PCR (one for each gene). The overall prevalence was 40.3%, 93.3% and 68.9% for the htr A, htr B and ppk 1 genes, respectively. Statistically significant differences were found ( p < 0.05) between prevalence of C. jejuni and C. coli for all three genes. In C. coli the prevalence was significantly higher for the htr A ( p = 0.007) and htr B ( p = 0.015) genes, while ppk 1 gene prevalence was significantly higher in C. jejuni ( p < 0.001). In addition, statistically significant increase in the frequency of htr A ( p = 0.007) and htr B ( p = 0.013) genes in the final product compared to broilers on arrival at the abattoir was observed in C. jejuni , but not in C. coli. These results suggest that htr A and htr B genes are involved in environmental persistence of Campylobacter jejuni.

New insights on Flaviporus (Polyporales) in the neotropics - Mauro C. Westphalen; Viviana Motato-Vásquez; Mario Rajchenberg; Michal Tomšovský; Adriana M. Gugliotta; Rosa Mara Borges da Silveira (Mycological Progress, 2022)

Sustained-release ketamine-loaded lipid-particulate system: in vivo assessment in mice - Weizhi Xu; Faheem Maqbool; Vinod Kumar; James R. Falconer; Cedric S. Cui; Trent M. Woodruff; Karin Borges; Andrew K. Whittaker; Maree T. Smith; Felicity Y. Han (Drug Delivery and Translational Research, 2022)

Of iconic animals and national pride: Whither restoration ecology in the Anthropocene? - Renee M Borges (Journal of Biosciences, 2022)

Induced Stress and Tactile Stimulation Applied to Primiparous does and their Consequences on Maternal Behavior, Human-Animal Relationships, and Future Offspringˊs Sexual Disorders - Angela C. F. Oliveira; Luiza M. Bernardi; Ana Larissa B. Monteiro; Kassy G. Silva; Saulo H. Weber; Tâmara D. Borges; Antoni Dalmau; Leandro B. Costa (Veterinary Research Communications, 2022)

Indoor-outdoor pollutant concentration modelling: a comprehensive urban air quality and exposure assessment - J. L. Santiago; E. Rivas; R. Buccolieri; A. Martilli; M. G. Vivanco; R. Borge; O. S. Carlo; F. Martín (Air Quality, Atmosphere & Health, 2022)
This paper is devoted to the investigation of the relationship between concentrations of traffic-related pollutants at pedestrian level in the street and indoor pollutant concentrations inside different rooms of different floors of a standard building. CFD modelling covering the whole urban environment, including the interior of a target building, is used to explicitly simulate wind flow and pollutant dispersion outdoors and indoors. A wide range of scenarios considering different percentage and location of open windows and different wind directions is investigated. A large variability of indoor pollutant concentrations is found depending on the floor and configuration of the open/closed windows, as well as the wind direction and its incidence angle. In general, indoor pollutant concentrations decrease with floor, but this decrease is different depending on the scenario and the room investigated. For some conditions, indoor concentrations higher than the spatially averaged values in the street (up to a ratio of 1.4) are found in some rooms due to the high pollutant concentrations close to open windows. This behavior may lead, on average, to higher exposure inside the room than outside although, in general, indoor pollutant concentrations are lower than that found in the street at pedestrian level. Results are averaged for all scenarios and rooms being the average ratio between indoor and oudoor concentrations 0.56 ± 0.24, which is in accordance with previous studies in real buildings. This paper opens to a unified approach for the assessment of air quality of the total indoor and outdoor environment.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Keystones to sustain life’s diversity - Renee M Borges (Journal of Biosciences, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Applying Mendelian randomization to appraise causality in relationships between nutrition and cancer - Kaitlin H. Wade; James Yarmolinsky; Edward Giovannucci; Sarah J. Lewis; Iona Y. Millwood; Marcus R. Munafò; Fleur Meddens; Kimberley Burrows; Joshua A. Bell; Neil M. Davies; Daniela Mariosa; Noora Kanerva; et al. (Cancer Causes & Control, 2022)
Dietary factors are assumed to play an important role in cancer risk, apparent in consensus recommendations for cancer prevention that promote nutritional changes. However, the evidence in this field has been generated predominantly through observational studies, which may result in biased effect estimates because of confounding, exposure misclassification, and reverse causality. With major geographical differences and rapid changes in cancer incidence over time, it is crucial to establish which of the observational associations reflect causality and to identify novel risk factors as these may be modified to prevent the onset of cancer and reduce its progression. Mendelian randomization (MR) uses the special properties of germline genetic variation to strengthen causal inference regarding potentially modifiable exposures and disease risk. MR can be implemented through instrumental variable (IV) analysis and, when robustly performed, is generally less prone to confounding, reverse causation and measurement error than conventional observational methods and has different sources of bias (discussed in detail below). It is increasingly used to facilitate causal inference in epidemiology and provides an opportunity to explore the effects of nutritional exposures on cancer incidence and progression in a cost-effective and timely manner. Here, we introduce the concept of MR and discuss its current application in understanding the impact of nutritional factors (e.g., any measure of diet and nutritional intake, circulating biomarkers, patterns, preference or behaviour) on cancer aetiology and, thus, opportunities for MR to contribute to the development of nutritional recommendations and policies for cancer prevention. We provide applied examples of MR studies examining the role of nutritional factors in cancer to illustrate how this method can be used to help prioritise or deprioritise the evaluation of specific nutritional factors as intervention targets in randomised controlled trials. We describe possible biases when using MR, and methodological developments aimed at investigating and potentially overcoming these biases when present. Lastly, we consider the use of MR in identifying causally relevant nutritional risk factors for various cancers in different regions across the world, given notable geographical differences in some cancers. We also discuss how MR results could be translated into further research and policy. We conclude that findings from MR studies, which corroborate those from other well-conducted studies with different and orthogonal biases, are poised to substantially improve our understanding of nutritional influences on cancer. For such corroboration, there is a requirement for an interdisciplinary and collaborative approach to investigate risk factors for cancer incidence and progression.

Zika virus infection of the placenta alters extracellular matrix proteome - Gabriel Borges-Vélez; Julio Rosado-Philippi; Yadira M. Cantres-Rosario; Kelvin Carrasquillo-Carrion; Abiel Roche-Lima; Jean Pérez-Vargas; Andrea González-Martínez; María S. Correa-Rivas; Loyda M. Meléndez (Journal of Molecular Histology, 2022)
Zika virus (ZIKV) infection has been associated with fetal abnormalities by compromising placental integrity, but the mechanisms by which this occurs are unknown. Flavivirus can deregulate the host proteome, especially extracellular matrix (ECM) proteins. We hypothesize that a deregulation of specific ECM proteins by ZIKV, affects placental integrity. Using twelve different placental samples collected during the 2016 ZIKV Puerto Rico epidemic, we compared the proteome of five ZIKV infected samples with four uninfected controls followed by validation of most significant proteins by immunohistochemistry. Quantitative proteomics was performed using tandem mass tag TMT10plex™ Isobaric Label Reagent Set followed by Q Exactive™ Hybrid Quadrupole Orbitrap Mass Spectrometry. Identification of proteins was performed using Proteome Discoverer 2.1. Proteins were compared based on the fold change and p value using Limma software. Significant proteins pathways were analyzed using Ingenuity Pathway (IPA). TMT analysis showed that ZIKV infected placentas had 94 reviewed differentially abundant proteins, 32 more abundant, and 62 less abundant. IPA analysis results indicate that 45 of the deregulated proteins are cellular components of the ECM and 16 play a role in its structure and organization. Among the most significant proteins in ZIKV positive placenta were fibronectin, bone marrow proteoglycan, and fibrinogen. Of these, fibrinogen was further validated by immunohistochemistry in 12 additional placenta samples and found significantly increased in ZIKV infected placentas. The upregulation of this protein in the placental tissue suggests that ZIKV infection is promoting the coagulation of placental tissue and restructuration of ECM potentially affecting the integrity of the tissue and facilitating dissemination of the virus from mother to the fetus.

A novel morphological phenotype does not ensure reduced biotic resistance on an oceanic island - M. Ferrante; R. Nunes; L. Lamelas-López; G. L. Lövei; P. A. V. Borges (Biological Invasions, 2022)

A comprehensive review on carotenoids in foods and feeds: status quo , applications, patents, and research needs - Antonio J. Meléndez-Martínez; Anamarija I. Mandić; Filippos Bantis; Volker Böhm; Grethe Iren A. Borge; Mladen Brnčić; Anette Bysted; M. Pilar Cano; M. Graça Dias; Anjo Elgersma; Martina Fikselová; Javier García-Alonso; et al. (Critical Reviews in Food Science and Nutrition, 2022)

Reproducibility and replicability in science: A Sisyphean task - Renee M Borges (Journal of Biosciences, 2022)

Highly Wet Chlorella minutissima Biomass for In Situ Biodiesel Production and Residual Biomass Rich in Labile Carbohydrates - Guilherme A. Pedro; Mateus S. Amaral; Felix M. Pereira; Danilo Luiz Flumignan; Patrícia C. M. Da Rós; Cristiano E. R. Reis; Messias Borges Silva (BioEnergy Research, 2022)

Connecting Amazonian historical biogeography and local assemblages of understorey birds: Recurrent guild proportionality within areas of endemism - Pilar L. M. Braga; Sérgio H. Borges; Carlos A. Peres; Bette A. Loiselle; John G. Blake; Juliana Menger; Anderson S. Bueno; Marina Anciães; Fernando H. Teófilo; Marina F. A. Maximiano; Affonso H. N. Souza; Roberta L. Boss; et al. (Journal of Biogeography, 2022)
Aim Current diversity patterns in local communities result from historical and contemporary events that operate at distinct spatial and temporal scales. However, the contribution of local and large‐scale processes in structuring species diversity remain a contentious topic in ecology. We investigated diversity patterns (species richness, composition and number of captures) of understorey bird assemblages in Amazonian unflooded ( terra firme ) forests. We sought to understand whether understorey bird assemblages in distinct areas of endemism show distinct patterns of diversity, and whether species replacements among areas of endemism occur while the proportion of species within guilds remains stable. Location Amazonia. Taxon Understorey birds. Methods To investigate diversity patterns, we compiled studies that mist‐netted birds at 11 regions across seven Amazonian areas of endemism. We used coverage‐based rarefaction curves, non‐metric multidimensional scaling (NMDS) and created a heatmap based on the proportion of captures in each area of endemism to access patterns of richness, composition and captures of understorey birds, respectively. The relative variance (RVgp index) was calculated to investigate the existence of guild proportionality within each area of endemism. Results Bird assemblages diverged across the seven areas of endemism, in terms of species richness, composition and captures. However, the proportion of species and individuals within guilds was similar among areas of endemism, indicating that species replacements across areas of endemism occur while maintaining the same ecological functions. Guild proportionality suggests that interspecific competition and resource availability are more important than environmental heterogeneity in structuring understorey bird assemblages. Main conclusions The similar proportion of species within guilds suggest that interspecific competition and resource availability are more important than environmental heterogeneity in structuring local assemblages, possibly via a process of limiting similarity in morphological and functional traits. The observed congruent structure in understorey bird assemblages across areas of endemism shows that coupled historical and ecological processes, operating at local to large scales, have led to current patterns of diversity and composition in Amazonian bird communities.

Reproductive benefits associated with dispersal in headwater populations of Trinidadian guppies ( Poecilia reticulata ) - Isabela L. Borges; Jillian C. Dangerfield; Lisa M. Angeloni; W. Chris Funk; Sarah W. Fitzpatrick (Ecology Letters, 2022)
Theory suggests that the evolution of dispersal is balanced by its fitness costs and benefits, yet empirical evidence is sparse due to the difficulties of measuring dispersal and fitness in natural populations. Here, we use spatially explicit data from a multi‐generational capture–mark–recapture study of two populations of Trinidadian guppies ( Poecilia reticulata ) along with pedigrees to test whether there are fitness benefits correlated with dispersal. Combining these ecological and molecular data sets allows us to directly measure the relationship between movement and reproduction. Individual dispersal was measured as the total distance moved by a fish during its lifetime. We analysed the effects of dispersal propensity and distance on a variety of reproductive metrics. We found that number of mates and number of offspring were positively correlated to dispersal, especially for males. Our results also reveal individual and environmental variation in dispersal, with sex, size, season, and stream acting as determining factors.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Zebrafish as a Tool for Studying Inflammation: A Systematic Review - M. A. P. Falcão; M. C. dos Santos Dantas; C. T. Rios; L. P. Borges; M. R. Serafini; A. G. Guimarães; C. I. B. Walker (Reviews in Fisheries Science & Aquaculture, 2022)

Biofilm formation under high shear stress increases resilience to chemical and mechanical challenges - L. C. Simões; I. B. Gomes; H. Sousa; A. Borges; M. Simões (Biofouling, 2022)

Editorial of Concern - Sara H. Sadok; Rayssa L. Borges-Medeiros; João R. M. de Oliveira (Journal of Molecular Neuroscience, 2022)

Understanding the behavior of sulfometuron-methyl in soils using multivariate analysis - Q. S. Pavão; M. d. Freitas Souza; T. M. S. Teófilo; H. A. Lins; M. P. S. Borges; T. S. Silva; A. B. R. Jesus Passos; V. Mendonça; D. V. Silva (International Journal of Environmental Science and Technology, 2022)

A picture is worth a thousand words: novel photographic evidence on the anatomy of the digestive system of three shipworm species (Bivalvia, Teredinidae) - L. M. S. Borges; B. Pfeifer; S. Pandur; D. Toubarro; A.-M. Tanase; I. Chiciudean; M. N. Menzel; M. Hoppert; R. Daniel; N. Simões; B. Altermark (Zoomorphology, 2021)

Acute exposition to Roundup Transorb® induces systemic oxidative stress and alterations in the expression of newly sequenced genes in silverside fish (Odontesthes humensis) - Amanda Weege S. Martins; Tony L. R. Silveira; Mariana H. Remião; William Borges Domingues; Eduardo N. Dellagostin; Antônio Sergio Varela Junior; Carine D. Corcini; Patrícia G. Costa; Adalto Bianchini; Gustavo M. Somoza; Ricardo B. Robaldo; Vinicius Farias Campos (Environmental Science and Pollution Research, 2021)

Combining Knowledge Systems Helps Understand the Spatial Dynamics of Data-Limited Small-Scale Fisheries Systems in Brazil: A Methods Analysis - Rebecca Borges; Indira A. L. Eyzaguirre; Roberta Sá Leitão Barboza; Karin Boos; Marion Glaser; Priscila F. M. Lopes (Frontiers in Marine Science, 2021)
Mangrove habitats provide nursery, shelter, and feeding sites for many economically relevant fish, and invertebrates, such as crabs. Given the highly artisanal character and the patchy spatial distribution of small-scale fishing in mangroves, there is often little data available to inform management, potentially threatening the sustainability of this livelihood-supporting activity. This study assesses the combination of different data collection methods and of including published data in the analysis of the spatial dynamics. We examine crab fisheries in two sustainable-use protected areas as a case study to understand use patterns as indicated by a specific combination of mapping methods. Mangrove crab fishing grounds were mapped by overlaying crab gatherers’ tracked routes with maps produced during participatory-mapping-centered interviews. Information from the literature was used to spatialize crab carapace width and relate it to distance traveled by fishers. Results show that crabs tended to be larger if caught farther from the villages where fishers live. In terms of collection methods, even though GPS tracking is relatively time- and resource-consuming, incorporating some GPS tracking into participatory mapping helps overcome a downside of this type of mapping (e.g., lack of geographical precision) and identifies information that can be accessed through participatory techniques. This highlights the importance of linking different approaches in order to understand small-scale fisheries spatial dynamics.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Optimization of a low-cost fertilizer-based medium for large-scale cultivation of the coastal diatom Conticribra weissflogii using response surface methodology and its effects on biomass composition - Cynthia Couto; Carlos Prentice Hernández; Rui Carlos M. Alves Sobrinho; Carlos Rafael Borges Mendes; Fabio Roselet; Paulo Cesar Abreu (Journal of Applied Phycology, 2021)

Large-scale Degradation of the Tocantins-Araguaia River Basin - Fernando Mayer Pelicice; Angelo Antonio Agostinho; Alberto Akama; José Dilermando Andrade Filho; Valter M. Azevedo-Santos; Marcus Vinicius Moreira Barbosa; Luis Mauricio Bini; Marcelo Fulgêncio Guedes Brito; Carlos Roberto dos Anjos Candeiro; Érica Pellegrini Caramaschi; Priscilla Carvalho; Rodrigo Assis de Carvalho; et al. (Environmental Management, 2021)

Role of bundle sheath conductance in sustaining photosynthesis competence in sugarcane plants under nitrogen deficiency - Vanessa R. Tofanello; Larissa M. Andrade; Denisele N. A. Flores-Borges; Eduardo Kiyota; Juliana L. S. Mayer; Silvana Creste; Eduardo C. Machado; Xinyou Yin; Paul C. Struik; Rafael V. Ribeiro (Photosynthesis Research, 2021)

Could soil granulometry and permeability drive the occurrence of the dune-dwelling ants from the genus Mycetophylax? - D. C. Cardoso; M. P. Cristiano; A. B. Borges-Silva; M. A. A. Carneiro (Insectes Sociaux, 2021)

Effect of lysed and non-lysed sickle red cells on the activation of NLRP3 inflammasome and LTB4 production by mononuclear cells - Thassila N. Pitanga; Sânzio S. Santana; Dalila L. Zanette; Caroline C. Guarda; Rayra P. Santiago; Vitor V. Maffili; Jonilson B. Lima; Graziele Q. Carvalho; Jaime R. Filho; Junia R. D. Ferreira; Milena M. Aleluia; Valma M. L. Nascimento; et al. (Inflammation Research, 2021)

Priming of indirect defence responses in maize is shown to be genotype-specific - Mirian F. F. Michereff; Priscila Grynberg; Roberto C. Togawa; Marcos M. C. Costa; Raúl A. Laumann; Jing-Jiang Zhou; Pedro H. C. Schimmelpfeng; Miguel Borges; John A. Pickett; Michael A. Birkett; Maria Carolina Blassioli-Moraes (Arthropod-Plant Interactions, 2021)

Not just a methane source: Amazonian floodplain sediments harbour a high diversity of methanotrophs with different metabolic capabilities - Júlia B. Gontijo; Fabiana S. Paula; Andressa M. Venturini; Caio A. Yoshiura; Clovis D. Borges; José Mauro S. Moura; Brendan J.M. Bohannan; Klaus Nüsslein; Jorge L. Mazza Rodrigues; Siu M. Tsai (Molecular Ecology, 2021)
The Amazonian floodplain forests are dynamic ecosystems of great importance for the regional hydrological and biogeochemical cycles and function as a significant CH 4 source contributing to the global carbon balance. Unique geochemical factors may drive the microbial community composition and, consequently, affect CH 4 emissions across floodplain areas. Here, we report the in situ composition of CH 4 cycling microbial communities in Amazonian floodplain sediments. We considered how abiotic factors may affect the microbial community composition and, more specifically, CH 4 cycling groups. We collected sediment samples during wet and dry seasons from three different types of floodplain forests, along with upland forest soil samples, from the Eastern Amazon, Brazil. We used high‐resolution sequencing of archaeal and bacterial 16S rRNA genes combined with real‐time PCR to quantify Archaea and Bacteria, as well as key functional genes indicative of the presence of methanogenic ( mcr A) and methanotrophic ( pmo A) microorganisms. Methanogens were found to be present in high abundance in floodplain sediments, and they seem to resist the dramatic environmental changes between flooded and nonflooded conditions. Methanotrophs known to use different pathways to oxidise CH 4 were detected, including anaerobic archaeal and bacterial taxa, indicating that a wide metabolic diversity may be harboured in this highly variable environment. The floodplain environmental variability, which is affected by the river origin, drives not only the sediment chemistry but also the composition of the microbial communities. These environmental changes seem also to affect the pools of methanotrophs occupying distinct niches. Understanding these shifts in the methanotrophic communities could improve our comprehension of the CH 4 emissions in the region.

Ventromedial prefrontal cortex CRF1 receptors modulate the tachycardic activity of baroreflex - João P. T. Brufatto; Davi C. Lagatta; Daniela L. Uliana; Egidi M. S. Firmino; Anna B. Borges-Assis; Leonardo B. M. Resstel (Pflügers Archiv - European Journal of Physiology, 2021)

Colletotrichum siamense as a causal agent of leaf anthracnose in seedlings of Annona muricata in nurseries from the Federal District, Brazil - Rafaela C. F. Borges; Maurício Rossato; Maria D. Mendes Santos; Mônica A. Macedo; M. E. N. Fonseca; L. S. Boiteux; A. Reis (Journal of Plant Diseases and Protection, 2021)

Effect of the hydroxamate group in the antitumoral activity and toxicity toward normal cells of new copper(II) complexes - Nathália F. B. Azeredo; Franz V. Borges; Marcelo S. Mathias; Jackson A. L. C. Resende; Roberto W. A. Franco; Milton M. Kanashiro; Adolfo Horn; Christiane Fernandes (BioMetals, 2021)

A strategy for the next decade to address data deficiency in neglected biodiversity - Axel Hochkirch; Michael J. Samways; Justin Gerlach; Monika Böhm; Paul Williams; Pedro Cardoso; Neil Cumberlidge; P. J. Stephenson; Mary B. Seddon; Viola Clausnitzer; Paulo A. V. Borges; Gregory M. Mueller; et al. (Conservation Biology, 2021)
Measuring progress toward international biodiversity targets requires robust information on the conservation status of species, which the International Union for Conservation of Nature (IUCN) Red List of Threatened Species provides. However, data and capacity are lacking for most hyperdiverse groups, such as invertebrates, plants, and fungi, particularly in megadiverse or high‐endemism regions. Conservation policies and biodiversity strategies aimed at halting biodiversity loss by 2020 need to be adapted to tackle these information shortfalls after 2020. We devised an 8‐point strategy to close existing data gaps by reviving explorative field research on the distribution, abundance, and ecology of species; linking taxonomic research more closely with conservation; improving global biodiversity databases by making the submission of spatially explicit data mandatory for scientific publications; developing a global spatial database on threats to biodiversity to facilitate IUCN Red List assessments; automating preassessments by integrating distribution data and spatial threat data; building capacity in taxonomy, ecology, and biodiversity monitoring in countries with high species richness or endemism; creating species monitoring programs for lesser‐known taxa; and developing sufficient funding mechanisms to reduce reliance on voluntary efforts. Implementing these strategies in the post‐2020 biodiversity framework will help to overcome the lack of capacity and data regarding the conservation status of biodiversity. This will require a collaborative effort among scientists, policy makers, and conservation practitioners.

Profiling of acetylcholinesterase inhibitory alkaloids from some Crinum , Habranthus and Zephyranthes species by GC–MS combined with multivariate analyses and in silico studies - Eman Shawky; Samah M. El Sohafy; Jean Paulo de Andrade; Warley de Souza Borges (Natural Product Research, 2021)

Guideline for the management of feline sporotrichosis caused by Sporothrix brasiliensis and literature revision - Isabella Dib Ferreira Gremião; Elisabeth Martins da Silva da Rocha; Hildebrando Montenegro; Aroldo José Borges Carneiro; Melissa Orzechowski Xavier; Marconi Rodrigues de Farias; Fabiana Monti; Wilson Mansho; Romeika Herminia de Macedo Assunção Pereira; Sandro Antonio Pereira; Leila M. Lopes-Bezerra (Brazilian Journal of Microbiology, 2021)

Bed nucleus of the stria terminalis modulates baroreflex cardiac activity: an interaction between alpha-1 receptors and NMDA/nitric oxide pathway - Davi C. Lagatta; Luciana B. Kuntze; Daniela L. Uliana; Anna B. Borges-Assis; Leonardo B. M. Resstel (Pflügers Archiv - European Journal of Physiology, 2021)

The Scent of Life: Phoretic Nematodes Use Wasp Volatiles and Carbon Dioxide to Choose Functional Vehicles for Dispersal - Satyajeet Gupta; Anusha L. K. Kumble; Kaveri Dey; Jean-Marie Bessière; Renee M. Borges (Journal of Chemical Ecology, 2021)

The decline of mussel aquaculture in the European Union: causes, economic impacts and opportunities - Lamprakis Avdelas; Edo Avdic‐Mravlje; Ana Cristina Borges Marques; Suzana Cano; Jacob J. Capelle; Natacha Carvalho; Maria Cozzolino; John Dennis; Tim Ellis; José M. Fernández Polanco; Jordi Guillen; Tobias Lasner; et al. (Reviews in Aquaculture, 2021)
In contrast to the increasing aquaculture production of mussels worldwide, production in the European Union (EU) has shown a decreasing trend over the last two decades. Aquaculture production of mussels in the EU peaked in the late 1990s at more than 600 000 tonnes; by 2016, production volume had dropped by 20% to 480 000 tonnes. As mussel production represents more than ⅓ of EU aquaculture production, this decrease is an important contributor to the stagnation of EU aquaculture. Previous studies have suggested diseases, lack of mussel seed (spat), and low profitability as the main causes of the EU mussel production decrease. In this study, we investigate how economic and environmental factors have contributed. Moreover, we examine if the different mussel production techniques (raft, longline, on‐bottom, and ‘bouchot’) have been differently affected, by analysing the economic performance and cost structure evolution for the period 2010–2016. We complement these results with a SWOT (strengths, weaknesses, opportunities, and threats) analysis of the EU mussel sector based on expert knowledge.

Caffeine has a dual influence on NMDA receptor–mediated glutamatergic transmission at the hippocampus - Robertta S. Martins; Diogo M. Rombo; Joana Gonçalves-Ribeiro; Carlos Meneses; Vladimir P. P. Borges-Martins; Joaquim A. Ribeiro; Sandra H. Vaz; Regina C. C. Kubrusly; Ana M. Sebastião (Purinergic Signalling, 2020)

Release-Recapture Test of Dispersal and Survival of Sterile Males of Ceratitis capitata (Diptera: Tephritidae) - F Duarte; M V Calvo; S Delgado; A Bartolucci; A Asfennato; A Borges; I Scatoni; F M García (Neotropical Entomology, 2020)

Soil microbial community, enzyme activity, C and N stocks and soil aggregation as affected by land use and soil depth in a tropical climate region of Brazil - Marcos V. M. Sarto; Wander L. B. Borges; Doglas Bassegio; Carlos A. B. Pires; Charles W. Rice; Ciro A. Rosolem (Archives of Microbiology, 2020)

Hydrocarbon Contamination Patterns in the Cenotes of the Mexican Caribbean: The Application of Principal Component Analysis - J. A. León-Borges; F. Viveros-Jiménez; A. E. Rodríguez-Mata; M. A. Lizardi-Jiménez (Bulletin of Environmental Contamination and Toxicology, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Deep soil carbon stock, origin, and root interaction in a tropical integrated crop–livestock system - Marcos V. M. Sarto; Wander L. B. Borges; Jaqueline R. W. Sarto; Charles W. Rice; Ciro A. Rosolem (Agroforestry Systems, 2020)

Microbial communities in anaerobic digesters change over time and sampling depth - Adriana Giongo; Camille E. Granada; Luiz G. A. Borges; Leandro M. Pereira; Fernanda J. Trindade; Shaiana P. Mattiello; Rafael R. Oliveira; Fauzi M. Shubeita; Adalberto Lovato; César Marcon; Renata Medina-Silva (Brazilian Journal of Microbiology, 2020)

Bi-Level Participatory Forest Management Planning Supported by Pareto Frontier Visualization - S Marques; V A Bushenkov; A V Lotov; M Marto; J G Borges (Forest Science, 2020)
This research addresses the problem of forested landscape management planning in contexts characterized by multiple ecosystem services and multiple stakeholders. A new methodology for participatory landscape-level forest management is proposed. Specifically, a bilevel representation is used, whereas models of subsystems are used for constructing an integrated model of the master problem. Participatory workshops and interactive visualization of the Pareto frontier are used to support the solution of the multi-objective optimization upper- and lower-level problems. The visualization is implemented by a technique—Interactive Decision Maps—that displays interactively the Pareto frontier in the form of decision maps, that is, collections of the objectives’ tradeoff curves. Since the upper-level problem may be characterized by a large number of decision variables, we compare the Pareto frontier generated by the Interactive Decision Maps technique with the Pareto frontier generated by a decomposition approach that builds from the Pareto frontiers of the lower-level subproblems. The approach supports further the negotiation between upper- and lower-level goals. Results are discussed for a large-scale application in a forested landscape in northwest Portugal.

Effect of phosphate availability on biofilm formation in cooling towers - Ingrid S. M. Pinel; Lan Hee Kim; Vitor R. Proença Borges; Nadia M. Farhat; Geert-Jan Witkamp; Mark C. M. van Loosdrecht; Johannes S. Vrouwenvelder (Biofouling, 2020)

The Value of Crop Production and Pollination Services in the Eastern Amazon - R C Borges; R M Brito; V L Imperatriz-Fonseca; T C Giannini (Neotropical Entomology, 2020)
Nature safeguards living organisms and the ecosystem functions and services delivered by them. Animal pollination is an important Ecosystem Service since it plays a key role for achieving the sustainable development goals by safeguarding worldwide food production. Thus, conservation of pollination services is a major priority for guaranteeing global food security in the long term. Here we evaluate the crop pollination services in Pará state (Eastern Amazon, Brazil) focusing on two questions: (1) What is the economic value of crop production and pollination service in Pará? (2) Which municipalities are most dependent on pollination services considering local economies? We found 36 crops produced in the state; 20 (55%) crops are dependent on animal pollinators. In 2016, crop production value (CPV) for Pará state was US$ 2.95 billion and total pollination service value (PSV) was US$ 983.2 million, corresponding to 33% of CPV in Pará. Highest PSV value crops were açaí palm (US$635.6 million), cocoa (US$187.6 million), soybean (US$98.4 million), and watermelon (US$26.1 million), accounting for 96% of Pará’s PSV. Two municipalities (Medicilândia and Igarapé Miri) presented more than 50% of their GDP based on pollination services. In general, we found low crop diversity in the municipalities of Pará, suggesting an economic rural vulnerability for the state, mainly supported by the high productions of soy and açaí. Pollinator conservation and ecological intensified farming practices are urgent for supporting sustainable development for the state.

Seasonal variation of surface radiation and energy balances over two contrasting areas of the seasonally dry tropical forest (Caatinga) in the Brazilian semi-arid - Camilla K. Borges; Carlos A. C. dos Santos; Rayonil G. Carneiro; Lindenberg L. da Silva; Gabriel de Oliveira; Denis Mariano; Madson T. Silva; Bernardo B. da Silva; Bergson G. Bezerra; Aldrin M. Perez-Marin; Salomão de S. Medeiros (Environmental Monitoring and Assessment, 2020)

A novel approach for subsurface characterization of coupled fluid flow and geomechanical deformation: the case of slightly compressible flows - M. R. Borges; F. Pereira (Computational Geosciences, 2020)

Evaluation of the anti-apoptotic activity of bovine alphaherpesvirus type 5 US3 protein kinase in insect cells using a recombinant baculovirus - Alice M. Silva; Fabrício S. Morgado; Leonardo A. Silva; José R. J. Borges; Simone Perecmanis; Daniel M. P. Ardisson-Araújo; Bergmann M. Ribeiro; Fabrício S. Campos (Brazilian Journal of Microbiology, 2020)

Human Losses and Damage Expected in Future Earthquakes on Faial Island–Azores - J. Fontiela; P. Rosset; M. Wyss; M. Bezzeghoud; J. Borges; F. Cota Rodrigues (Pure and Applied Geophysics, 2020)

Influence of dietary fermented Saccharomyces cerevisiae on growth performance, oxidative stress parameters, and immune response of cultured Oreochromis niloticus - Nermeen M. Abu-Elala; Nehal A. Younis; Huda O. AbuBakr; Naela M. Ragaa; Liliana L. Borges; Melina A. Bonato (Fish Physiology and Biochemistry, 2020)

Preliminary study on the response of marine fungoid protists, the thraustochytrids, to lipid extracts of diatoms - Varada S. Damare; Priya M. D’Costa; Mamatha S. Shivaramu; Vilda Borges; Mary Fernandes; Charmaine Fernandes; Svetlana Cardozo (Aquatic Ecology, 2020)

Male-Produced Sex Pheromone of Tibraca limbativentris Revisited: Absolute Configurations of Zingiberenol Stereoisomers and their Influence on Chemotaxis Behavior of Conspecific Females - M. C. Blassioli-Moraes; A. Khrimian; M. F. F. Michereff; D. M. Magalhães; E. Hickel; T. F. S. de Freitas; J. A. F. Barrigossi; R. A. Laumann; A. T. Silva; S. D. Guggilapu; C. C. Silva; J. Sant’Ana; et al. (Journal of Chemical Ecology, 2020)

Biogeographical history of the genus Atherina (Pisces: Atherinidae) in the central Eastern Atlantic - S. Moreno-Borges; A. Brito; S. M. Francisco (Marine Biodiversity, 2019)

Does Sugarcane Straw Removal Change the Abundance of Soil Microbes? - Maristela C. Morais; Beatriz M. Ferrari; Clovis D. Borges; Maurício R. Cherubin; Siu Mui Tsai; Carlos C. Cerri; Carlos E. P. Cerri; Brigitte J. Feigl (BioEnergy Research, 2019)

Unifying macroecology and macroevolution to answer fundamental questions about biodiversity - Brian J. McGill; Jonathan M. Chase; Joaquín Hortal; Isaac Overcast; Andrew J. Rominger; James Rosindell; Paulo A. V. Borges; Brent C. Emerson; Rampal S. Etienne; Michael J. Hickerson; D. Luke Mahler; Francois Massol; et al. (Global Ecology and Biogeography, 2019)
The study of biodiversity started as a single unified field that spanned both ecology and evolution and both macro and micro phenomena. But over the 20th century, major trends drove ecology and evolution apart and pushed an emphasis towards the micro perspective in both disciplines. Macroecology and macroevolution re‐emerged as self‐consciously distinct fields in the 1970s and 1980s, but they remain largely separated from each other. Here, we argue that despite the challenges, it is worth working to combine macroecology and macroevolution. We present 25 fundamental questions about biodiversity that are answerable only with a mixture of the views and tools of both macroecology and macroevolution.

Long-Term Spatial–Temporal Characterization of Cloud-to-Ground Lightning in the Metropolitan Region of Rio de Janeiro - Tales Bernardes Paulucci; Gutemberg Borges França; Renata Libonati; Alexandre M. Ramos (Pure and Applied Geophysics, 2019)

Effect of male aggressivity profile on female chemical choice in Nile tilapia - V. S. Rossi; M. Borges de Sá; V. S. Sugihara; I. M. de Mello; P. C. Giaquinto (Journal of Ethology, 2019)

Global Patterns of Species Richness in Coastal Cephalopods - Rui Rosa; Vasco Pissarra; Francisco O. Borges; José Xavier; Ian G. Gleadall; Alexey Golikov; Giambattista Bello; Liliane Morais; Fedor Lishchenko; Álvaro Roura; Heather Judkins; Christian M. Ibáñez; et al. (Frontiers in Marine Science, 2019)

Insights into the Bidirectional Properties of the Sheep–Deer Prion Transmission Barrier - Chafik Harrathi; Natalia Fernández-Borges; Hasier Eraña; Saioa R. Elezgarai; Vanessa Venegas; Jorge M. Charco; Joaquín Castilla (Molecular Neurobiology, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Effects of Probiotic Supplementation on Trimethylamine-N-Oxide Plasma Levels in Hemodialysis Patients: a Pilot Study - Natália A. Borges; P. Stenvinkel; P. Bergman; A. R. Qureshi; B. Lindholm; C. Moraes; M. B. Stockler-Pinto; D. Mafra (Probiotics and Antimicrobial Proteins, 2019)

Early Interaction of Alternaria infectoria Conidia with Macrophages - M. C. Almeida; D. Antunes; B. M. A. Silva; L. Rodrigues; M. Mota; O. Borges; C. Fernandes; T. Gonçalves (Mycopathologia, 2019)

Downregulation of CD163 in monocytes and its soluble form in the plasma is associated with a pro-inflammatory profile in pregnant women with preeclampsia - Priscila R. Nunes; Mariana Romão-Veiga; José C. Peraçoli; Roberto A. Araujo Costa; Leandro G. de Oliveira; Vera Therezinha M. Borges; Maria Terezinha Peraçoli (Immunologic Research, 2019)

Influence of constitutive and induced volatiles from mature green coffee berries on the foraging behaviour of female coffee berry borers, Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae) - M. C. Blassioli-Moraes; M. F. F. Michereff; D. M. Magalhães; S. D. Morais; M. J. Hassemer; R. A. Laumann; A. M. Meneghin; M. A. Birkett; D. M. Withall; J. N. Medeiros; C. M. C. Corrêa; M. Borges (Arthropod-Plant Interactions, 2019)

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Crown gall caused by Agrobacterium tumefaciens species complex: a novel nursery disease of Tectona grandis in Brazil - Rafaela C. F. Borges; Maurício Rossato; Greecy Mirian R. Albuquerque; Maria A. Ferreira; Ana C. M. Brasileiro; Maria Esther N. Fonseca; Leonardo Silva Boiteux (Journal of Plant Pathology, 2019)

A leaf spot of Tectona grandis caused by Xanthomonas fuscans in Brazil - Rafaela C. F. Borges; Maurício Rossato; Maria do Desterro M. Santos; Cléia S. Cabral; Greecy Mirian R. Albuquerque; Maria A. Ferreira; Maria Esther N. Fonseca; Leonardo Silva Boiteux (Journal of Plant Pathology, 2019)

Variability in herbivore-induced defence signalling across different maize genotypes impacts significantly on natural enemy foraging behaviour - Mirian F. F. Michereff; Diego M. Magalhães; Marla J. Hassemer; Raúl A. Laumann; Jing-Jiang Zhou; Paulo E. de A. Ribeiro; Paulo A. Viana; Paulo E. de O. Guimarães; Pedro H. C. Schimmelpfeng; Miguel Borges; John A. Pickett; Michael A. Birkett; et al. (Journal of Pest Science, 2019)

Differential expression of miRNAs related to angiogenesis and adipogenesis in subcutaneous fat of obese and nonobese women - Aline S. Gasparotto; Diego O. Borges; Marina G. M. Sassi; Adriana Milani; Darwin L. Rech; Marcia Terres; Pedro B. Ely; Mauricio J. Ramos; Nelson G. Meihnardt; Vanessa S. Mattevi (Molecular Biology Reports, 2019)

Combined transcriptomics–metabolomics profiling of the heat shock response in the hyperthermophilic archaeon Pyrococcus furiosus - Ana M. Esteves; Gonçalo Graça; Lindsay Peyriga; Inês M. Torcato; Nuno Borges; Jean-Charles Portais; Helena Santos (Extremophiles, 2019)

Beyond the Last Glacial Maximum: Island endemism is best explained by long‐lasting archipelago configurations - Sietze J. Norder; Konstantinos Proios; Robert J. Whittaker; María R. Alonso; Paulo A. V. Borges; Michael K. Borregaard; Robert H. Cowie; F. B. Vincent Florens; António M. de Frias Martins; Miguel Ibáñez; W. Daniel Kissling; Lea de Nascimento; et al. (Global Ecology and Biogeography, 2019)
Aim To quantify the influence of past archipelago configuration on present‐day insular biodiversity patterns, and to compare the role of long‐lasting archipelago configurations over the Pleistocene to configurations of short duration such as at the Last Glacial Maximum (LGM) and the present‐day. Location 53 volcanic oceanic islands from 12 archipelagos worldwide—Azores, Canary Islands, Cook Islands, Galápagos, Gulf of Guinea, Hawaii, Madeira, Mascarenes, Pitcairn, Revillagigedo, Samoan Islands and Tristan da Cunha. Time period The last 800 kyr, representing the nine most recent glacial–interglacial cycles. Major taxa studied Land snails and angiosperms. Methods Species richness data for land snails and angiosperms were compiled from existing literature and species checklists. We reconstructed archipelago configurations at the following sea levels: the present‐day high interglacial sea level, the intermediate sea levels that are representative of the Pleistocene and the low sea levels of the LGM. We fitted two alternative linear mixed models for each archipelago configuration using the number of single‐island endemic, multiple‐island endemic and (non‐endemic) native species as a response. Model performance was assessed based on the goodness‐of‐fit of the full model, the variance explained by archipelago configuration and model parsimony. Results Single‐island endemic richness in both taxonomic groups was best explained by intermediate palaeo‐configuration (positively by area change, and negatively by palaeo‐connectedness), whereas non‐endemic native species richness was poorly explained by palaeo‐configuration. Single‐island endemic richness was better explained by intermediate archipelago configurations than by the archipelago configurations of the LGM or present‐day. Main conclusions Archipelago configurations at intermediate sea levels—which are representative of the Pleistocene—have left a stronger imprint on single‐island endemic richness patterns on volcanic oceanic islands than extreme archipelago configurations that persisted for only a few thousand years (such as the LGM). In understanding ecological and evolutionary dynamics of insular biota it is essential to consider longer‐lasting environmental conditions, rather than extreme situations alone.

Local hypoxia generated by live burial is effective in weed control within termite fungus farms - L. Katariya; P. B. Ramesh; A. Sharma; R. M. Borges (Insectes Sociaux, 2018)

Distinct patterns of exocytosis elicited by Ca2+, Sr2+ and Ba2+ in bovine chromaffin cells - Andrés M. Baraibar; Ricardo de Pascual; Marcial Camacho; Natalia Domínguez; J. David Machado; Luis Gandía; Ricardo Borges (Pflügers Archiv - European Journal of Physiology, 2018)

Gaseous and liquid effluents treatment in bubble column reactors by advanced oxidation processes: A review - Vanessa N. Lima; Carmen S. D. Rodrigues; Ricardo A. C. Borges; Luis M. Madeira (Critical Reviews in Environmental Science and Technology, 2018)

Dimethyl Fumarate Prevents HIV-Induced Lysosomal Dysfunction and Cathepsin B Release from Macrophages - Lester J. Rosario-Rodríguez; Krystal Colón; Gabriel Borges-Vélez; Karla Negrón; Loyda M. Meléndez (Journal of Neuroimmune Pharmacology, 2018)

Development and validation of diagrammatic scale to assess target spot severity in cotton - L. H. Fantin; K. Braga; M. G. Canteri; A. R. Dias; E. P. Borges (Australasian Plant Pathology, 2018)

Comparison of Vegetative Bioremediation and Chemical Amendments for Non-calcareous Highly Saline-Sodic Soil Remediation - João M. Jesus; Anthony S. Danko; António Fiúza; Maria-Teresa Borges (Water, Air, & Soil Pollution, 2018)

Lactobacillus spp. impair the ability of Listeria monocytogenes FBUNT to adhere to and invade Caco-2 cells - P. Castellano; M. Pérez Ibarreche; L. Longo Borges; F. C. Niño Arias; G. R. Ross; E. C. Pereira De Martinis (Biotechnology Letters, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Substrate-borne vibrations disrupt the mating behaviors of the neotropical brown stink bug, Euschistus heros: implications for pest management - R. A. Laumann; D. H. B. Maccagnan; A. Čokl; M. C. Blassioli-Moraes; M. Borges (Journal of Pest Science, 2018)

Fungal Diversity of Human Gut Microbiota Among Eutrophic, Overweight, and Obese Individuals Based on Aerobic Culture-Dependent Approach - Francis M. Borges; Thaís O. de Paula; Marjorie R. A. Sarmiento; Maycon G. de Oliveira; Maria L. M. Pereira; Isabela V. Toledo; Thiago C. Nascimento; Alessandra B. Ferreira-Machado; Vânia L. Silva; Cláudio G. Diniz (Current Microbiology, 2018)

Age Influence on Sexual Behavior of the Lesser Cornstalk Borer, Elasmopalpus lignosellus (Zeller) (Lepidoptera: Pyralidae) - L M S Xavier; D M Magalhães; P A Viana; M C Blassioli-Moraes; M Borges; J A F Barrigossi; E F Vilela; R A Laumann (Neotropical Entomology, 2018)

Microbiota associated with tubes of Escarpia sp. from cold seeps in the southwestern Atlantic Ocean constitutes a community distinct from that of surrounding marine sediment and water - Renata Medina-Silva; Rafael R. Oliveira; Fernanda J. Trindade; Luiz G. A. Borges; Taiz L. Lopes Simão; Adolpho H. Augustin; Fernanda P. Valdez; Marcelo J. Constant; Carolina L. Simundi; Eduardo Eizirik; Claudia Groposo; Dennis J. Miller; et al. (Antonie van Leeuwenhoek, 2018)

Dynamic environments of fungus‐farming termite mounds exert growth‐modulating effects on fungal crop parasites - Lakshya Katariya; Priya B. Ramesh; Renee M. Borges (Environmental Microbiology, 2018)
Summary This study investigated for the first time the impact of the internal mound environment of fungus‐growing termites on the growth of fungal crop parasites. Mounds of the termite Odontotermes obesus acted as (i) temperature and relative humidity (RH) ‘stabilisers’ showing dampened daily variation and (ii) ‘extreme environments’ exhibiting elevated RH and CO 2 levels, compared to the outside. Yet, internal temperatures exhibited seasonal dynamics as did daily and seasonal CO 2 levels. During in situ experiments under termite‐excluded conditions within the mound, the growth of the crop parasite Pseudoxylaria was greater inside than outside the mound, i.e., Pseudoxylaria is ‘termitariophilic’. Also, ex situ experiments on parasite isolates differing in growth rates and examined under controlled conditions in the absence of termites revealed a variable effect with fungal growth decreasing only under high CO 2 and low temperature conditions, reflecting the in situ parasite growth fluctuations. In essence, the parasite appears to be adapted to survive in the termite mound. Thus the mound microclimate does not inhibit the parasite but the dynamic environmental conditions of the mound affect its growth to varying extents. These results shed light on the impact of animal‐engineered structures on parasite ecology, independent of any direct role of animal engineers.

A fig tree in a concrete jungle: fine-scale population genetic structure of the cluster fig Ficus racemosa in an urban environment - Anusha Krishnan; Renee M. Borges (Urban Ecosystems, 2018)

Effect of plants in constructed wetlands for organic carbon and nutrient removal: a review of experimental factors contributing to higher impact and suggestions for future guidelines - João M. Jesus; Anthony S. Danko; António Fiúza; Maria-Teresa Borges (Environmental Science and Pollution Research, 2018)

Pre-culture in endothelial growth medium enhances the angiogenic properties of adipose-derived stem/stromal cells - Lucas E. B. Souza; Liziane R. Beckenkamp; Lays M. Sobral; Daianne M. C. Fantacini; Fernanda U. F. Melo; Josiane S. Borges; Andréia M. Leopoldino; Simone Kashima; Dimas Tadeu Covas (Angiogenesis, 2018)

Coupling biological detection to liquid chromatography: a new tool in drug discovery - M. A. Campuzano-Bublitz; J. G. Hernández-Jiménez; R. González-Brito; M. S. Montesinos; J. J. Fernández; J. G. Díaz; R. Borges (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Determination of avidity of IgG against protein antigens from Streptococcus pneumoniae: assay development and preliminary application in clinical settings - D. C. Andrade; I. C. Borges; N. Ekström; T. Jartti; T. Puhakka; A. Barral; H. Kayhty; O. Ruuskanen; C. M. Nascimento-Carvalho (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

History Matters: Oviposition Resource Acceptance in an Exploiter of a Nursery Pollination Mutualism - Pratibha Yadav; Sathish Desireddy; Srinivasan Kasinathan; Jean-Marie Bessière; Renee M. Borges (Journal of Chemical Ecology, 2018)

The Inclusion of Chitosan in Poly-ε-caprolactone Nanoparticles: Impact on the Delivery System Characteristics and on the Adsorbed Ovalbumin Secondary Structure - Sandra Jesus; Elizangela H. Fragal; Adley F. Rubira; Edvani C. Muniz; Artur J. M. Valente; Olga Borges (AAPS PharmSciTech, 2018)

Protein requirements of collared peccary (Pecari tajacu) - Rogério M. Borges; Alcester Mendes; Selene S. C. Nogueira; Jérôme Bindelle; Sérgio L. G. Nogueira-Filho (Tropical Animal Health and Production, 2017)

Use of 3D printing for biofuel production: efficient catalyst for sustainable biodiesel production from wastes - M. E. Borges; L. Hernández; J. C. Ruiz-Morales; P. F. Martín-Zarza; J. L. G. Fierro; P. Esparza (Clean Technologies and Environmental Policy, 2017)

Fungus-Farming Termites Selectively Bury Weedy Fungi that Smell Different from Crop Fungi - Lakshya Katariya; Priya B. Ramesh; Thejashwini Gopalappa; Sathish Desireddy; Jean-Marie Bessière; Renee M. Borges (Journal of Chemical Ecology, 2017)

Co-niche construction between hosts and symbionts: ideas and evidence - Renee M. Borges (Journal of Genetics, 2017)

Coupling fire behaviour modelling and stand characteristics to assess and mitigate fire hazard in a maritime pine landscape in Portugal - B. Botequim; P. M. Fernandes; J. Garcia-Gonzalo; A. Silva; J. G. Borges (European Journal of Forest Research, 2017)

Solar photocatalysis at semi-pilot scale: wastewater decontamination in a packed-bed photocatalytic reactor system with a visible-solar-light-driven photocatalyst - M. E. Borges; M. Sierra; P. Esparza (Clean Technologies and Environmental Policy, 2017)

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Seasonal patterns and association of meteorological factors with infection caused by Streptococcus pneumoniae , Haemophilus influenzae , and Moraxella catarrhalis in childhood community-acquired pneumonia in a tropical region - Igor C. Borges; Dafne C. Andrade; Maria-Regina A. Cardoso; Andreas Meinke; Aldina Barral; Helena Käyhty; Olli Ruuskanen; Cristiana M. Nascimento-Carvalho (Infectious Diseases, 2017)

Nonneurological Involvement in Late-Onset Friedreich Ataxia (LOFA): Exploring the Phenotypes - Alberto R. M. Martinez; Adriana Moro; Agessandro Abrahao; Ingrid Faber; Conrado R. Borges; Thiago J. R. Rezende; Carlos R. Martins; Mariana Moscovich; Renato P. Munhoz; Sandra Leistner Segal; Walter O. Arruda; Maria Luiza Saraiva-Pereira; et al. (The Cerebellum, 2017)

A new species of Hepatozoon Miller, 1908 (Apicomplexa: Adelerina) from the snake Philodryas nattereri Steindachner (Squamata: Dipsadidae) in northeastern Brazil - Diva M. Borges-Nojosa; M. Juliana Borges-Leite; João P. Maia; Djan Zanchi-Silva; Roberta da Rocha Braga; D. James Harris (Systematic Parasitology, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Phytochemical profiling as a solution to palliate disinfectant limitations - J. Malheiro; I. Gomes; A. Borges; M. M. S. M. Bastos; J.-Y. Maillard; F. Borges; M. Simões (Biofouling, 2016)

Topography‐driven isolation, speciation and a global increase of endemism with elevation - Manuel J. Steinbauer; Richard Field; John‐Arvid Grytnes; Panayiotis Trigas; Claudine Ah‐Peng; Fabio Attorre; H. John B. Birks; Paulo A. V. Borges; Pedro Cardoso; Chang‐Hung Chou; Michele De Sanctis; Miguel M. de Sequeira; et al. (Global Ecology and Biogeography, 2016)
Aim Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location Thirty‐two insular and 18 continental elevational gradients from around the world. Methods We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic (‘percent endemism’) in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.

Biodegradation Pathway of the Pyrethroid Pesticide Esfenvalerate by Bacteria from Different Biomes - Willian G. Birolli; Eloá M. Borges; Marcia Nitschke; Luciane P. C. Romão; André L. M. Porto (Water, Air, & Soil Pollution, 2016)

Geographic structuring into vicariant species-pairs in a wide-ranging, high-dispersal plant–insect mutualism: the case of Ficus racemosa and its pollinating wasps - A. Bain; R. M. Borges; M. H. Chevallier; H. Vignes; N. Kobmoo; Y. Q. Peng; A. Cruaud; J. Y. Rasplus; F. Kjellberg; M. Hossaert-Mckey (Evolutionary Ecology, 2016)

The role of plant fidelity and land-use changes on island exotic and indigenous canopy spiders at local and regional scales - Margarita Florencio; François Rigal; Paulo A. V. Borges; Pedro Cardoso; Ana M. C. Santos; Jorge M. Lobo (Biological Invasions, 2016)

Inversion of ambient seismic noise HVSR to evaluate velocity and structural models of the Lower Tagus Basin, Portugal - J. F. Borges; H. G. Silva; R. J. G. Torres; B. Caldeira; M. Bezzeghoud; J. A. Furtado; J. Carvalho (Journal of Seismology, 2016)

Assessment and comparison of the properties of biodiesel synthesized from three different types of wet microalgal biomass - Katkam N. Gangadhar; Hugo Pereira; Hermínio P. Diogo; Rui M. Borges dos Santos; B. L. A. Prabhavathi Devi; R. B. N. Prasad; Luísa Custódio; F. Xavier Malcata; João Varela; Luísa Barreira (Journal of Applied Phycology, 2016)

Antinociceptive effect of a novel armed spider peptide Tx3-5 in pathological pain models in mice - Sara M. Oliveira; Cássia R. Silva; Gabriela Trevisan; Jardel G. Villarinho; Marta N. Cordeiro; Michael Richardson; Márcia H. Borges; Célio J. Castro; Marcus V. Gomez; Juliano Ferreira (Pflügers Archiv - European Journal of Physiology, 2016)

Influence of Two Acyclic Homoterpenes (Tetranorterpenes) on the Foraging Behavior of Anthonomus grandis Boh - D. M. Magalhães; M. Borges; R. A. Laumann; C. M. Woodcock; J. A. Pickett; M. A. Birkett; Maria Carolina Blassioli-Moraes (Journal of Chemical Ecology, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

The internal structure of the pallets of Nototeredo norvagica and Psiloteredo megotara (Bivalvia: Teredinidae): implications for subfamilial allocations - L. M. S. Borges (Zoomorphology, 2016)

Oxidative mitigation of aquatic methane emissions in large Amazonian rivers - Henrique O. Sawakuchi; David Bastviken; André O. Sawakuchi; Nicholas D. Ward; Clovis D. Borges; Siu M. Tsai; Jeffrey E. Richey; Maria Victoria R. Ballester; Alex V. Krusche (Global Change Biology, 2016)
The flux of methane ( CH 4 ) from inland waters to the atmosphere has a profound impact on global atmospheric greenhouse gas ( GHG ) levels, and yet, strikingly little is known about the dynamics controlling sources and sinks of CH 4 in the aquatic setting. Here, we examine the cycling and flux of CH 4 in six large rivers in the A mazon basin, including the A mazon R iver. Based on stable isotopic mass balances of CH 4 , inputs and outputs to the water column were estimated. We determined that ecosystem methane oxidation ( MOX ) reduced the diffusive flux of CH 4 by approximately 28–96% and varied depending on hydrologic regime and general geochemical characteristics of tributaries of the Amazon River. For example, the relative amount of MOX was maximal during high water in black and white water rivers and minimal in clear water rivers during low water. The abundance of genetic markers for methane‐oxidizing bacteria ( pmoA ) was positively correlated with enhanced signals of oxidation, providing independent support for the detected MOX patterns. The results indicate that MOX in large Amazonian rivers can consume from 0.45 to 2.07 Tg CH 4 yr −1 , representing up to 7% of the estimated global soil sink. Nevertheless, climate change and changes in hydrology, for example, due to construction of dams, can alter this balance, influencing CH 4 emissions to atmosphere.

Structure and toxicity of clozapine and olanzapine on agranulocytosis - Rosivaldo S. Borges; Gláucio R. Nagurniak; Luana M. D. Queiroz; Cristiane S. F. Maia; Carlos A. L. Barros; Ednilsom Orestes; Albérico B. F. da Silva (Medicinal Chemistry Research, 2016)

Evidence for multiple founding lineages and genetic admixture in the evolution of species within an oceanic island weevil (Coleoptera, Curculionidae) super‐radiation - Christiana M. A. Faria; Antonio Machado; Isabel R. Amorim; Matthew J. G. Gage; Paulo A. V. Borges; Brent C. Emerson (Journal of Biogeography, 2016)
Aim To infer colonization and speciation history for a closely related complex of nine species within the enigmatic Canary Island Laparocerus weevil radiation of 128 species. Using molecular dating and the spatial and temporal context that islands provide, we evaluate the possible explanations of incomplete lineage sorting and gene flow for the origin of shared genetic variation among species from different islands. Location Canary Islands (Gran Canaria, Tenerife, La Palma and El Hierro). Methods We collected a total of 173 specimens from 37 sites distributed across the four islands. Phylogenetic analyses of mitochondrial ( COII ) and nuclear ( ITS 2) sequence data and molecular dating techniques were used to infer the origin of the group in the archipelago and their history of colonization and differentiation. Results Gran Canaria appeared to be the geographical origin of the complex. An unexpected result was that mt DNA revealed each of the single species on La Palma and El Hierro to be the product of more than one colonization event from more than one source island. In both cases nuclear ITS 2 data revealed these multiple colonizations to have been followed by admixture. Main conclusions The two gene trees present very different topologies, with a rather simple colonization history required to explain the pattern of nuclear gene relationships, while the mt DNA gene tree implicates a much more complex history of colonization. Explanations of incomplete lineage sorting are ruled out and a history of colonization and speciation for the L. tessellatus complex involving genetic admixture is inferred.

A Bayesian framework for the validation of models for subsurface flows: synthetic experiments - M. Akbarabadi; M. Borges; A. Jan; F. Pereira; M. Piri (Computational Geosciences, 2015)

Plant reproductive traits mediate tritrophic feedback effects within an obligate brood-site pollination mutualism - Anusha Krishnan; Mahua Ghara; Srinivasan Kasinathan; Gautam Kumar Pramanik; Santosh Revadi; Renee M. Borges (Oecologia, 2015)

Emergence of azole-resistant Candida albicans in small ruminants - R. S. N. Brilhante; S. T. C. Silva; D. S. C. M. Castelo-Branco; C. E. C. Teixeira; L. C. Borges; P. V. Bittencourt; J. S. de Oliveira; A. J. Monteiro; T. J. P. G. Bandeira; R. A. Cordeiro; J. L. B. Moreira; J. J. C. Sidrim; et al. (Mycopathologia, 2015)

Ground-Motion Simulation in the Lower Tagus Valley Basin - J. F. Borges; M. Bezzeghoud; B. Caldeira; João Carvalho (Pure and Applied Geophysics, 2015)

Geostatistics and Geographic Information Systems to Study the Spatial Distribution of Grapholita molesta (Busck) (Lepidoptera: Tortricidae) in Peach Fields - F Duarte; M V Calvo; A Borges; I B Scatoni (Neotropical Entomology, 2015)

Effects of palatable cafeteria diet on cognitive and noncognitive behaviors and brain neurotrophins’ levels in mice - Daniela D. Leffa; Samira S. Valvassori; Roger B. Varela; Jésica Lopes-Borges; Francine Daumann; Luiza M. Longaretti; Ana Luiza F. Dajori; João Quevedo; Vanessa M. Andrade (Metabolic Brain Disease, 2015)

Linking Brazil’s food security policies to agricultural change - Johan A. Oldekop; M. Jahi Chappell; Felipe E. Borges Peixoto; Adriano Pereira Paglia; Marina Schmoeller do Prado Rodrigues; Karl L. Evans (Food Security, 2015)

Detection of antibody responses against Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis proteins in children with community-acquired pneumonia: effects of combining pneumococcal antigens, pre-existing antibody levels, sampling interval, age, and duration of illness - I. C. Borges; D. C. Andrade; A.-L. Vilas-Boas; M.-S. H. Fontoura; H. Laitinen; N. Ekström; P. V. Adrian; A. Meinke; M.-R. A. Cardoso; A. Barral; O. Ruuskanen; H. Käyhty; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Experimental infection of inbred BALB/c and A/J mice with Massachusetts and Brazilian strains of infectious bronchitis virus (IBV) - Matheus C. Martini; Jacy Gameiro; Tereza Cristina Cardoso; Leonardo C. Caserta; Ana Carolina M. Gualberto; Lara Borges Keid; Trícia M. F. de S. Oliveira; Marcia M. A. B. dos Santos; Clarice W. Arns; Helena L. Ferreira (Archives of Virology, 2015)

Phytoremediation of salt-affected soils: a review of processes, applicability, and the impact of climate change - João M. Jesus; Anthony S. Danko; António Fiúza; Maria-Teresa Borges (Environmental Science and Pollution Research, 2015)

Electrochemical sensor for simultaneous determination of herbicide MCPA and its metabolite 4-chloro-2-methylphenol. Application to photodegradation environmental monitoring - V. Rahemi; J. M. P. J. Garrido; F. Borges; C. M. A. Brett; E. M. P. J. Garrido (Environmental Science and Pollution Research, 2015)

Exploratory experiments to determine the effect of alternative operations on the efficiency of subsurface arsenic removal in rural Bangladesh - M. M. Rahman; M. Bakker; S. C. Borges Freitas; D. van Halem; B. M. van Breukelen; K. M. Ahmed; A. B. M. Badruzzaman (Hydrogeology Journal, 2015)

Novel isomannide-based peptide mimetics containing a tartaric acid backbone as serine protease inhibitors - Bárbara Abrahim-Vieira; Emmerson C. B. da Costa; Pedro H. R. de A. Azevedo; Aline C. Portela; Luiza R. S. Dias; Sergio Pinheiro; Amilcar Tanuri; Anne M. Capaccia; Gustavo T. Ventura; Ronaldo Mohana-Borges; Carlos R. Rodrigues; Alessandra M. T. de Souza; et al. (Medicinal Chemistry Research, 2014)

Determination of stress-induced degradation products of cetirizine dihydrochloride by a stability-indicating RP-HPLC method - Paloma Flórez Borges; Pilar Pérez Lozano; Encarna García Montoya; Montserrat Miñarro; Josep R Ticó; Enric Jo; Josep M Suñe Negre (DARU Journal of Pharmaceutical Sciences, 2014)

Influence of the Anaerobic Biodegradation of Different Types of Biodiesel on the Natural Attenuation of Benzene - J. M. Borges; J. M. Dias; A. S. Danko (Water, Air, & Soil Pollution, 2014)

The broadcast spawning Caribbean shipworm, Teredothyra dominicensis (Bivalvia, Teredinidae), has invaded and become established in the eastern Mediterranean Sea - J. Reuben Shipway; Luisa M. S. Borges; Johann Müller; Simon M. Cragg (Biological Invasions, 2014)

Mannosylglycerate: structural analysis of biosynthesis and evolutionary history - Nuno Borges; Carla D. Jorge; Luís G. Gonçalves; Susana Gonçalves; Pedro M. Matias; Helena Santos (Extremophiles, 2014)

Critical swimming speeds of wild‐caught sand‐smelt Atherina presbyter larvae - A. M. Faria; R. Borges; E. J. Gonçalves (Journal of Fish Biology, 2014)
Swimming abilities of wild‐caught sand‐smelt Atherina presbyter larvae were assessed as critical swimming speed ( U crit ) throughout ontogeny. The mean U crit increased with size, ranging from 3·6 to 18·7 cm s −1 , over the size range of 6·6–21·0 mm L T . This indicates that at hatching A. presbyter larvae, far from being passive floaters, are already capable of active behaviours, which may influence their dispersal patterns.

Production of dissolved organic matter by phytoplankton and its uptake by heterotrophic prokaryotes in large tropical lakes - Cedric Morana; Hugo Sarmento; Jean-Pierre Descy; Josep M. Gasol; Alberto V. Borges; Steven Bouillon; François Darchambeau (Limnology and Oceanography, 2014)
In pelagic ecosystems, phytoplankton extracellular release can extensively subsidize the heterotrophic prokaryotic carbon demand. Time‐course experiments were carried out to quantify primary production, phytoplankton excretion, and the microbial uptake of freshly released dissolved organic carbon (DOC) derived from phytoplankton extracellular release (DOCp) in four large tropical lakes distributed along a productivity gradient: Kivu, Edward, Albert, and Victoria. The contributions of the major heterotrophic bacterial groups to the uptake of DOCp was also analyzed in Lake Kivu, using microautoradiography coupled to catalyzed reporter deposition fluorescent in situ hybridization. The percentage of extracellular release (PER) varied across the productivity gradient, with higher values at low productivity. Furthermore, PER was significantly related to high light and low phosphate concentrations in the mixed layer and was comparatively higher in oligotrophic tropical lakes than in their temperate counterparts. Both observations suggest that environmental factors play a key role in the control of phytoplankton excretion. Standing stocks of DOCp were small and generally contributed less than 1% to the total DOC because it was rapidly assimilated by prokaryotes. In other words, there was a tight coupling between the production and the heterotrophic consumption of DOCp. None of the major phylogenetic bacterial groups that were investigated differed in their ability to take up DOCp, in contrast with earlier results reported for standard labeled single‐molecule substrates (leucine, glucose, adenosine triphosphate). It supports the idea that the metabolic ability to use DOCp is widespread among heterotrophic prokaryotes. Overall, these results highlight the importance of carbon transfer between phytoplankton and bacterioplankton in large African lakes.

To what extent are the fish compositions of a regulated river related to physico-chemical variables and habitat structure? - Taylan M. Mattos; Marcus R. Costa; B. C. T. Pinto; Joyce L. C. Borges; F. Gerson Araújo (Environmental Biology of Fishes, 2014)

Divvying up an incubator: How parasitic and mutualistic fig wasps use space within their nursery microcosm - Mahua Ghara; Yuvaraj Ranganathan; Anusha Krishnan; Vishwas Gowda; Renee M. Borges (Arthropod-Plant Interactions, 2014)

Identification and Expression Profile of Two Putative Odorant-Binding Proteins from the Neotropical Brown Stink Bug, Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) - L R Farias; D P Paula; J J Zhou; R Liu; G J Pappas; M C B Moraes; R A Laumann; M Borges; M A Birkett; J A Pickett; L M Field; S N Báo (Neotropical Entomology, 2014)

Seismicity along the Azores-Gibraltar region and global plate kinematics - M. Bezzeghoud; C. Adam; E. Buforn; J. F. Borges; B. Caldeira (Journal of Seismology, 2014)

Using flow cytometry and cytological analyses to assess the genetic stability of somatic embryo-derived plantlets from embryogenic Musa acuminata Colla (AA) ssp. malaccensis cell suspension cultures - Rosa M. Escobedo-GraciaMedrano; Josefina I. Maldonado-Borges; Martha J. Burgos-Tan; Nina Valadez-González; José R. Ku-Cauich (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Photocatalysis as a potential tertiary treatment of urban wastewater: new photocatalytic materials - M. E. Borges; T. Hernández; P. Esparza (Clean Technologies and Environmental Policy, 2014)

Determination of stress-induced degradation products of cetirizine dihydrochloride by a stability-indicating RP-HPLC method - Paloma Flórez Borges; Pilar Pérez Lozano; Encarna García Montoya; Montserrat Miñarro; Josep R Ticó; Enric Jo; Josep M Suñe Negre (DARU Journal of Pharmaceutical Sciences, 2014)

Ground motion simulations of the SW Iberia margin: rupture directivity and earth structure effects - M. Bezzeghoud; J. F. Borges; B. Caldeira (Natural Hazards, 2013)

Mating Behavior of Mahanarva spectabilis (Hemiptera: Cercopidae) Under Laboratory Conditions - Marcy G. Fonseca; Sandra E. B. Silva; Alexander M. Auad; Iris G. Paiva; Cristiano A. V. Borges (Journal of Insect Behavior, 2013)

Steroidal aromatase inhibitors inhibit growth of hormone-dependent breast cancer cells by inducing cell cycle arrest and apoptosis - Cristina Amaral; Carla Varela; Margarida Borges; Elisiário Tavares da Silva; Fernanda M. F. Roleira; Georgina Correia-da-Silva; Natércia Teixeira (Apoptosis, 2013)

Cytotoxic constituents from the stem bark of Diospyros cuneata Standl. - C. Quintal-Novelo; R.E. Moo-Puc; J. Chale-Dzul; M. Cáceres-Farfán; M. Mendez-Gonzalez; R. Borges-Argáez (Natural Product Research, 2013)

Conceptualizing a mountain hydrogeologic system by using an integrated groundwater assessment (Serra da Estrela, Central Portugal): a review - Jorge Espinha Marques; José M. Marques; Helder I. Chaminé; Paula M. Carreira; Paulo E. Fonseca; Fernando A. Monteiro Santos; Rui Moura; Javier Samper; Bruno Pisani; José Teixeira; José Martins Carvalho; Fernando Rocha; et al. (Geosciences Journal, 2013)

Effects of acute and chronic administration of fenproporex on DNA damage parameters in young and adult rats - Cinara L. Gonçalves; Gislaine T. Rezin; Gabriela K. Ferreira; Isabela C. Jeremias; Mariane R. Cardoso; Samira S. Valvassori; Bruna J. P. Munhoz; Gabriela D. Borges; Bruno N. Bristot; Daniela D. Leffa; Vanessa M. Andrade; João Quevedo; et al. (Molecular and Cellular Biochemistry, 2013)

A new dimeric naphthoquinone from Diospyros anisandra - A.H. Uc-Cachón; G.M. Molina-Salinas; S. Said-Fernández; M. Méndez-González; M. Cáceres-Farfán; R. Borges-Argáez (Natural Product Research, 2013)

Effect of l-Tyrosine In Vitro and In Vivo on Energy Metabolism Parameters in Brain and Liver of Young Rats - Gabriela K. Ferreira; Giselli Scaini; Milena Carvalho-Silva; Lara M. Gomes; Lislaine S. Borges; Júlia S. Vieira; Larissa S. Constantino; Gustavo C. Ferreira; Patrícia F. Schuck; Emilio L. Streck (Neurotoxicity Research, 2013)

Diel Variation in Fig Volatiles Across Syconium Development: Making Sense of Scents - Renee M. Borges; Jean-Marie Bessière; Yuvaraj Ranganathan (Journal of Chemical Ecology, 2013)

How do different dispersal modes shape the species–area relationship? Evidence for between‐group coherence in the M acaronesian flora - Silvia C. Aranda; Rosalina Gabriel; Paulo A. V. Borges; Ana M. C. Santos; Joaquín Hortal; Andrés Baselga; Jorge M. Lobo (Global Ecology and Biogeography, 2013)
Aim We explore the island species–area relationships ( ISARs ) of several plant groups differing in dispersal ability. We examine whether: (i) the ISAR slope is higher for less dispersive groups (diminishing from not‐wind‐dispersed seed plants to wind‐dispersed seed plants, pteridophytes and bryophytes); and (ii) the regional richness is higher than that predicted by the ISAR of its constituent islands for groups with lower dispersal ability. Additionally, we relate both patterns to the compositional dissimilarity (beta diversity) between islands. Location The M acaronesian archipelagos of the A zores, M adeira and C anary I slands. Methods ISARs were estimated using the conventional power model. Differences in slopes among taxa were analysed through ANCOVA tests. We assessed the deviation of the total richness of the M acaronesian flora from that predicted by the ISAR and calculated several measures of beta diversity (turnover, nestedness‐resultant dissimilarity and nestedness). Analyses were repeated after excluding the two C anarian islands of L anzarote and F uerteventura, which have unique climatic and geological conditions in the region. Results All ISAR models were significant except for pteridophytes (for which it was significant when excluding L anzarote and F uerteventura). ISAR slopes did not differ among taxa. Regional richness followed ISAR predictions for bryophytes and pteridophytes when L anzarote and F uerteventura were excluded, while the total number of M acaronesian seed plants (particularly not‐wind‐dispersed species) always fell above the ISAR . Turnover was higher in seed plants than in bryophytes and pteridophytes, and the opposite occurred with nestedness. Main conclusions Differences in dispersal ability influence the compositional dissimilarity between these islands, but not the rate of species increase with area. This may be because ISAR slopes are mostly determined by within‐island processes of species accumulation, while differences in dispersal generate different between‐island patterns. The lack of relationship between the ISAR slope and species replacement or nestedness prevents its use as a proxy for beta diversity.

Catalytic Packed-Bed Reactor Configuration for Biodiesel Production Using Waste Oil as Feedstock - M. E. Borges; L. Díaz (BioEnergy Research, 2013)

Semiochemicals from Herbivory Induced Cotton Plants Enhance the Foraging Behavior of the Cotton Boll Weevil, Anthonomus grandis - D. M. Magalhães; M. Borges; R. A. Laumann; E. R. Sujii; P. Mayon; J. C. Caulfield; C. A. O. Midega; Z. R. Khan; J. A. Pickett; M. A. Birkett; M. C. Blassioli-Moraes (Journal of Chemical Ecology, 2012)

Gene copy number and differential gene expression in haploid and diploid males of the stingless bee, Melipona quadrifasciata - A. A. Borges; F. C. Humann; M. G. Tavares; L. A. O. Campos; K. Hartfelder (Insectes Sociaux, 2012)

Characterization of cuticular hydrocarbons of diploid and haploid males, workers and queens of the stingless bee Melipona quadrifasciata - A. A. Borges; M. J. Ferreira-Caliman; F. S. Nascimento; L. A. O. Campos; M. G. Tavares (Insectes Sociaux, 2012)

Population of Scaptocoris castanea Perty (Hemiptera: Cydnidae) in a Crop–Livestock Integration System - Marcelo Francisco Arantes Pereira; R M Peres; Rodrigo dos Santos Borges (Neotropical Entomology, 2012)

An electronic study of pyrazolones drugs on agranulocytosis - J. Rodrigues Silva; A. Noronha Queiroz; E. A. Fontes Junior; M. V. Santos Silva; A. Manoel Herculano; A. M. J. Chaves Neto; R. Santos Borges (Medicinal Chemistry Research, 2012)

Sex Pheromone Communication in Two Sympatric Neotropical Stink Bug Species Chinavia ubica and Chinavia impicticornis - M. C. Blassioli-Moraes; R. A. Laumann; M. W. M. Oliveira; C. M. Woodcock; P. Mayon; A. Hooper; J. A. Pickett; M. A. Birkett; M. Borges (Journal of Chemical Ecology, 2012)

Resolving the Azorean knot: a response to Carine & Schaefer (2010) - Kostas A. Triantis; Joaquín Hortal; Isabel Amorim; Pedro Cardoso; Ana M. C. Santos; Rosalina Gabriel; Paulo A. V. Borges (Journal of Biogeography, 2012)
Carine & Schaefer ( Journal of Biogeography , 2010, 37 , 77–89) suggest that the lack of past climate oscillations in the Azores may have contributed to the low plant endemism in this archipelago compared to that of the Canary Islands, a pattern they term the Azorean diversity enigma. Here we challenge their hypothesis, and discuss how the particular characteristics of the Azores may have driven current diversification patterns in this archipelago. We argue that the restricted number of Azorean endemic species and their wide distribution is explicable by the geological, geographical and ecological attributes of the archipelago. That is, the Azores are too young, too small, and too environmentally homogeneous to have hosted many in situ diversification events, so they do not host as many endemic species as other Macaronesian archipelagos, such as Madeira and especially the Canary Islands.

A simple protocol for cryopreservation of zygotic embryos of ten accessions of coconut (Cocos nucifera L.) - O. N’Nan; M. Borges; J.-L. Konan Konan; V. Hocher; J.-L. Verdeil; J. Tregear; A. S. P. N’guetta; F. Engelmann; B. Malaurie (In Vitro Cellular & Developmental Biology - Plant, 2012)

Water Remediation Using Calcium Phosphate Derived From Marine Residues - Eduardo A. Borges da Silva; Carina A. E. Costa; Vítor J. P. Vilar; Cidália M. S. Botelho; Mohamed B. Larosi; Juan M. P. Saracho; Rui A. R. Boaventura (Water, Air, & Soil Pollution, 2012)

Isotopic fractionation between seawater and the shell of Scrobicularia plana (Bivalvia) and its application for age validation - Sílvia Santos; Joana F. M. F. Cardoso; Valeska Borges; Rob Witbaard; Pieternella C. Luttikhuizen; Henk W. van der Veer (Marine Biology, 2012)

Determination of pesticides and their metabolites in processed cereal samples - M.Á. González-Curbelo; J. Hernández-Borges; T.M. Borges-Miquel; M.Á. Rodríguez-Delgado (Food Additives & Contaminants: Part A, 2012)

Composition of Extrafloral Nectar Influences Interactions between the Myrmecophyte Humboldtia brunonis and its Ant Associates - Megha Shenoy; Venkatesan Radhika; Suma Satish; Renee M. Borges (Journal of Chemical Ecology, 2012)

An enterprise architecture approach to forest management support systems design: an application to pulpwood supply management in Portugal - A. F. Marques; J. G. Borges; P. Sousa; A. M. Pinho (European Journal of Forest Research, 2011)

Characterization of wildfires in Portugal - S. Marques; J. G. Borges; J. Garcia-Gonzalo; F. Moreira; J. M. B. Carreiras; M. M. Oliveira; A. Cantarinha; B. Botequim; J. M. C. Pereira (European Journal of Forest Research, 2011)

Simultaneous phenanthrene and cadmium removal from contaminated soil by a ligand/biosurfactant solution - Tânia M. S. Lima; Lorena C. Procópio; Felipe D. Brandão; André M. X. Carvalho; Marcos R. Tótola; Arnaldo C. Borges (Biodegradation, 2011)

The Azores archipelago, Portugal: improved understanding of small island coastal hazards and mitigation measures - H. Calado; P. Borges; M. Phillips; K. Ng; F. Alves (Natural Hazards, 2011)

Studies in a Fixed-Bed Photocatalytic Reactor System Using Natural Materials for Degradation of a Dye Contaminant in Water - P. Esparza; M. E. Borges; L. Díaz (Water, Air, & Soil Pollution, 2011)

Biodegradability of bacterial surfactants - Tânia M. S. Lima; Lorena C. Procópio; Felipe D. Brandão; André M. X. Carvalho; Marcos R. Tótola; Arnaldo C. Borges (Biodegradation, 2011)

Management of chestnut plantations for a multifunctional land use under Mediterranean conditions: effects on productivity and sustainability - A. Martins; G. Marques; O. Borges; E. Portela; J. Lousada; F. Raimundo; M. Madeira (Agroforestry Systems, 2011)

The Azorean Biodiversity Portal: An internet database for regional biodiversity outreach - PAULO A.V. BORGES †; ROSALINA GABRIEL †; ANA M. ARROZ †; ANA COSTA †; REGINA T. CUNHA †; LUÍS SILVA †; ENÉSIMA MENDONÇA †; ANTÓNIO M. F. MARTINS †; FRANCISCO REIS †; PEDRO CARDOSO † (Systematics and Biodiversity, 2010)

Bond-based linear indices of the non-stochastic and stochastic edge-adjacency matrix. 1. Theory and modeling of ChemPhys properties of organic molecules - Yovani Marrero-Ponce; Eugenio R. Martínez-Albelo; Gerardo M. Casañola-Martín; Juan A. Castillo-Garit; Yunaimy Echevería-Díaz; Vicente Romero Zaldivar; Jan Tygat; José E. Rodriguez Borges; Ramón García-Domenech; Francisco Torrens; Facundo Pérez-Giménez (Molecular Diversity, 2010)

Microsatellite Polymorphisms in Cassava Landraces from the Cerrado Biome, Mato Grosso do Sul, Brazil - M. V. B. M. Siqueira; T. T. Pinheiro; A. Borges; T. L. Valle; M. Zatarim; E. A. Veasey (Biochemical Genetics, 2010)

Assessing the completeness of bryophytes inventories: an oceanic island as a case study (Terceira, Azorean archipelago) - Silvia C. Aranda; Rosalina Gabriel; Paulo A. V. Borges; Jorge M. Lobo (Biodiversity and Conservation, 2010)

Higher dopamine transporter density in Parkinson’s disease patients with depression - Andre C. Felicio; Tais S. Moriyama; Clecio Godeiro-Junior; Ming C. Shih; Marcelo Q. Hoexter; Vanderci Borges; Sonia M. A. Silva; Edson Amaro-Junior; Luiz A. F. Andrade; Henrique B. Ferraz; Rodrigo A. Bressan (Psychopharmacology, 2010)

Are species–area relationships from entire archipelagos congruent with those of their constituent islands? - Ana M. C. Santos; Robert J. Whittaker; Kostas A. Triantis; Paulo A. V. Borges; Owen R. Jones; Donald L. J. Quicke; Joaquín Hortal (Global Ecology and Biogeography, 2010)
Aim To establish the extent to which archipelagos follow the same species–area relationship as their constituent islands and to explore the factors that may explain departures from the relationship. Location Thirty‐eight archipelagos distributed worldwide. Methods We used ninety‐seven published datasets to create island species–area relationships (ISARs) using the Arrhenius logarithmic form of the power model. Observed and predicted species richness of an archipelago and of each of its islands were used to calculate two indices that determined whether the archipelago followed the ISAR. Archipelagic residuals ( ArcRes ) were calculated as the residual of the prediction provided by the ISAR using the total area of the archipelago, standardized by the total richness observed in the archipelago. We also tested whether any characteristic of the archipelago (geological origin and isolation) and/or taxon accounts for whether an archipelago fits into the ISAR or not. Finally, we explored the relationship between ArcRes and two metrics of nestedness. Results The archipelago was close to the ISAR of its constituent islands in most of the cases analysed. Exceptions arose for archipelagos where (i) the slopes of the ISAR are low, (ii) observed species richness is higher than expected by the ISAR and/or (iii) distance to the mainland is small. The archipelago's geological origin was also important; a higher percentage of oceanic archipelagos fit into their ISAR than continental ones. ArcRes indicated that the ISAR underpredicts archipelagic richness in the least isolated archipelagos. Different types of taxon showed no differences in ArcRes . Nestedness and ArcRes appear to be related, although the form of the relationship varies between metrics. Main conclusions Archipelagos, as a rule, follow the same ISAR as their constituent islands. Therefore, they can be used as distinct units themselves in large‐scale biogeographical and macroecological studies. Departure from the ISAR can be used as a crude indicator of richness‐ordered nestedness, responsive to factors such as isolation, environmental heterogeneity, number and age of islands.

Genetic and clonal diversity of the endemic ant-plant Humboldtia brunonis (Fabaceae) in the Western Ghats of India - Suma A. Dev; Megha Shenoy; Renee M. Borges (Journal of Biosciences, 2010)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

Effects of soil management practices and irrigation on plant water relations and productivity of chestnut stands under Mediterranean conditions - A. Martins; F. Raimundo; O. Borges; I. Linhares; V. Sousa; J. P. Coutinho; J. Gomes-Laranjo; M. Madeira (Plant and Soil, 2010)

Spatiotemporal variations of f CO 2 in the North Sea - A. M. Omar; A. Olsen; T. Johannessen; M. Hoppema; H. Thomas; A. V. Borges (Ocean Science, 2010)
Data from two Voluntary Observing Ship (VOS) (2005–2007) augmented with data subsets from ten cruises (1987–2005) were used to investigate the spatiotemporal variations of the CO2 fugacity in seawater (fCO2sw) in the North Sea at seasonal and inter-annual time scales. The observed seasonal fCO2sw variations were related to variations in sea surface temperature (SST), biology plus mixing, and air-sea CO2 exchange. Over the study period, the seasonal amplitude in fCO2sw induced by SST changes was 0.4–0.75 times those resulting from variations in biology plus mixing. Along a meridional transect, fCO2sw normally decreased northwards (−12 μatm per degree latitude), but the gradient disappeared/reversed during spring as a consequence of an enhanced seasonal amplitude of fCO2sw in southern parts of the North Sea. Along a zonal transect, a weak gradient (−0.8 μatm per degree longitude) was observed in the annual mean fCO2sw. Annually and averaged over the study area, surface waters of the North Sea were CO2 undersaturated and, thus, a sink of atmospheric CO2. However, during summer, surface waters in the region 55.5–54.5° N were CO2 supersaturated and, hence, a source for atmospheric CO2. Comparison of fCO2sw data acquired within two 1°×1° regions in the northern and southern North Sea during different years (1987, 2001, 2002, and 2005–2007) revealed large interannual variations, especially during spring and summer when year-to-year fCO2sw differences (≈160–200 μatm) approached seasonal changes (≈200–250 μatm). The springtime variations resulted from changes in magnitude and timing of the phytoplankton bloom, whereas changes in SST, wind speed and total alkalinity may have contributed to the summertime interannual fCO2sw differences. The lowest interannual variation (10–50 μatm) was observed during fall and early winter. Comparison with data reported in October 1967 suggests that the fCO2sw growth rate in the central North Sea was similar to that in the atmosphere.

Phenotypic plasticity and longevity in plants and animals: cause and effect? - Renee M. Borges (Journal of Biosciences, 2009)

Of pungency, pain, and naked mole rats: chili peppers revisited - Renee M. Borges (Journal of Biosciences, 2009)

Abnormal meiosis in tetraploid genotypes ofBrachiaria brizantha (Poaceae) induced by colchicine: its implications for breeding - A. B. Mendes-Bonato; M. Ferrari Felismino; A. M. Souza Kaneshima; C. Pessim; V. Calisto; M. Suely Pagliarini; C. Borges do Valle (Journal of Applied Genetics, 2009)

Visual ecology of Indian carpenter bees II: adaptations of eyes and ocelli to nocturnal and diurnal lifestyles - Hema Somanathan; Almut Kelber; Renee M. Borges; Rita Wallén; Eric J. Warrant (Journal of Comparative Physiology A, 2009)

Perception of ultraviolet light by crab spiders and its role in selection of hunting sites - Ramachandra M. Bhaskara; C. M. Brijesh; Saveer Ahmed; Renee M. Borges (Journal of Comparative Physiology A, 2009)

Seasonal Variability of Carbon Dioxide in the Rivers and Lagoons of Ivory Coast (West Africa) - Y. J. M. Koné; G. Abril; K. N. Kouadio; B. Delille; A. V. Borges (Estuaries and Coasts, 2009)

Vehicular particulate matter emissions in road tunnels in Sao Paulo, Brazil - Odón R. Sánchez-Ccoyllo; Rita Y. Ynoue; Leila D. Martins; Rosana Astolfo; Regina M. Miranda; Edmilson D. Freitas; Alessandro S. Borges; Adalgiza Fornaro; Helber Freitas; Andréa Moreira; Maria F. Andrade (Environmental Monitoring and Assessment, 2009)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Visual ecology of Indian carpenter bees I: Light intensities and flight activity - Hema Somanathan; Renee M. Borges; Eric J. Warrant; Almut Kelber (Journal of Comparative Physiology A, 2008)

A novel mutualism between an ant-plant and its resident pollinator - Megha Shenoy; Renee M. Borges (The Science of Nature, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Male Ant-mimicking Salticid Spiders Discriminate Between Retreat Silks of Sympatric Females: Implications for Pre-mating Reproductive Isolation - Renee M. Borges; Saveer Ahmed; C. Veena Prabhu (Journal of Insect Behavior, 2007)

Modelling of the dyeing process of packed cotton threads using reactive dyes - Selene M. A. Guelli Ulson de Souza; Dilênio Pacheco de Souza; Eduardo Alberto Borges da Silva; Antônio Augusto Ulson de Souza (Transport in Porous Media, 2007)

Pictures at an exhibition: Bees view Van Gogh’sSunflowers - Renee M. Borges (Journal of Biosciences, 2006)

Organic carbon metabolism and carbonate dynamics in a Mediterranean seagrass (Posidonia oceanica), meadow - Cristina Barrón; Carlos M. Duarte; Michel Frankignoulle; Alberto Vieira Borges (Estuaries and Coasts, 2006)

Molluscan diversity caught by trawling fisheries: a case study in southern Portugal - M. A. E. MALAQUIAS; L. BENTES; K. ERZINI; T. C. BORGES (Fisheries Management and Ecology, 2006)
The effects of commercial trawling on the malacological communities (except for the Cephalopoda) were examined, based on a study undertaken between 1996 and 2000 on the continental shelf and slope of southern Portugal. More than 50% of species caught by trawling in southern Portugal were discarded, with molluscs representing about 19%. Forty‐four species of molluscs (15 bivalves, 28 gastropods and one polyplacophoran) were identified from the discarded specimens. Crustacean trawlers accounted for 34 molluscs species, and fish trawlers for 24. Twenty species were only caught by the crustacean trawl, compared with 10 species by the fish trawl, and 14 species were common to both trawls. The bivalve Venus nux Gmelin was the most numerous species discarded in the fish trawl, accounting for 42.0% of the total number of individuals, followed by the gastropods Ampulla priamus (Meuschen) (7.8%) and Ranella olearium (L.) (7.3%). In the crustacean trawl, the most numerous species discarded were the bivalve Anadara diluvii (Lamarck) (19.4%), the gastropod Calliostoma granulatum (Born) (15.5%), and the bivalve V. nux (15.1%). The third most discarded species from fish trawls in Algarve waters, the gastropod species R. olearium , is a species listed in Annex II of the Bern Convention. The difficulties of managing the real impact of fisheries on the molluscan populations and in defining a conservation strategy are discussed.

Invasibility and species richness of island endemic arthropods: a general model of endemic vs. exotic species - Paulo A. V. Borges; Jorge M. Lobo; Eduardo B. de Azevedo; Clara S. Gaspar; Catarina Melo; Luis V. Nunes (Journal of Biogeography, 2006)
Aim This paper has two objectives. First, we examine how a variety of biotic, abiotic and anthropogenic factors influence the endemic and introduced arthropod richness on an oceanic island. Second, we look at the relationship between the endemic and introduced arthropod richness, to ask whether areas with high levels of endemic species richness deter invasions. Location The work was carried out on a young volcanic island, Terceira, in the Azores. Methods We used standard techniques to collect data on arthropod species richness. Environmental data were obtained from the CIELO climatic model and using GIS. The explanatory value of environmental variables on a small‐scale gradient of endemic and exotic arthropod species richness was examined with generalized linear models (GLMs). In addition, the impact of both endemic and exotic species richness in the communities was assessed by entering them after the environmental variable(s) to see if they contributed significantly to the final model (the hierarchical method). Results Abiotic (climatic and geomorphological) variables gave a better explanation of the variation in endemic species richness, whereas anthropogenic variables explained most of the variation in introduced species richness. Furthermore, after accounting for all environmental variables, part of the unexplained variance in the endemic species richness is explained by the introduced species richness and vice‐versa. That is, areas with high levels of endemic species richness had many introduced species. There is evidence of a somewhat inverse spatial distribution between a group of oceanic‐type, forest‐dwelling, endemic, relict arthropods and a group of more generalist endemic arthropods that are able to survive in disturbed marginal sites particularly rich in non‐indigenous species. Main conclusions Richness of endemic species is mainly driven by abiotic factors such as a climatic axis (oceanic‐type localities with lower temperatures and summer precipitations) and a binary variable CALD (location of sites in caldeiras or ravines), whereas richness of introduced species depends on disturbance related factors. However, after factoring out these major influences, there is a correlation between endemic and introduced richness, suggesting that – independent of the environmental and geographical factors that affect the distribution of endemic or introduced species – the richest endemic assemblages are more prone to invasion, due probably to a facilitation process. Inconclusive evidence suggests that non‐indigenous species are limited to those sites under anthropogenic influence located mainly near forest edges, but the rate of expansion of those species to high‐altitude, core pristine sites has still to be tested.

Genetic Heterogeneity in Trypanosoma cruzi Strains From Naturally Infected Triatomine Vectors in Northeastern Brazil: Epidemiological Implications - Raquel S. Pacheco; Célia M. Marques de Brito; Otilia Sarquis; Marize Q. Pires; José Borges-Pereira; Marli M. Lima (Biochemical Genetics, 2005)

The fitness consequences of bearing domatia and having the right ant partner: experiments with protective and non-protective ants in a semi-myrmecophyte - Laurence Gaume; Merry Zacharias; Vladimir Grosbois; Renee M. Borges (Oecologia, 2005)

Do plants and animals differ in phenotypic plasticity? - Renee M. Borges (Journal of Biosciences, 2005)

Segmentation of the fibro-glandular disc in mammogrms using Gaussian mixture modelling - R. J. Ferrari; R. M. Rangayyan; R. A. Borges; A. F. Frère (Medical & Biological Engineering & Computing, 2004)

Identification of the breast boundary in mammograms using active contour models - R. J. Ferrari; A. F. Frère; R. M. Rangayyan; J. E. L. Desautels; R. A. Borges (Medical & Biological Engineering & Computing, 2004)

Regeneration and multiplication of Dioscorea alata germplasm maintained in vitro - M. Borges; W. Ceiro; S. Meneses; N. Aguilera; J. Vázquez; Z. Infante; M. Fonseca (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Hepatotoxicity of 3,4-methylenedioxyamphetamine and ?-methyldopamine in isolated rat hepatocytes: formation of glutathione conjugates - Maria Lourdes Bastos; Mrcia Carvalho; Nuno Milhazes; Fernando Remio; Fernanda Borges; Eduarda Fernandes; Francisco Amado; Terrence J. Monks; Flix Carvalho (Archives of Toxicology, 2004)

Acute Effects of Vanadate Oligomers on Heart, Kidney, and Liver Histology in the Lusitanian Toadfish (Halobatrachus didactylus) - G. Borges; P. Mendona; N. Joaquim; J. Coucelo; M. Aureliano (Archives of Environmental Contamination and Toxicology, 2003)

Butterfly pollination and high-contrast visual signals in a low-density distylous plant - Renee M. Borges; Vinita Gowda; Merry Zacharias (Oecologia, 2003)

Changes in the distribution of sardine eggs and larvae off Portugal, 1985–2000 - Y. Stratoudakis; M. Bernal; D. L. Borchers; M. F. Borges (Fisheries Oceanography, 2003)
Generalized additive models (GAMs) were fitted to sardine ( Sardina pilchardus ) egg distribution data from three daily egg production method surveys. The results showed that the area of egg cover off Portugal decreased significantly from 11 800 km 2 in 1988 to 7000 km 2 in 1997 and 7400 km 2 in 1999. This is because of a significant reduction in sardine egg presence off northern Portugal, GAM estimated areas being similar or higher in the late 1990s for southwestern and southern Portugal. The distributional area covered by larvae was not estimated for 1988 (larval distribution extended beyond the survey area), although it was probably higher than the 9600 km 2 for 1997 and 5500 km 2 for 1999. In 1997 and 1999, the Gulf of Cadiz was also sampled, indicating extensive areas with sardine eggs and larvae (more than 50% of the total area of distribution off Portugal). Standardized data from 15 ichthyoplankton surveys between 1985 and 2000 show a decline in the mean probability of egg presence within the Portuguese continental shelf from the mid‐1980s to the late‐1990s, because of a marked reduction in egg presence off northern Portugal. Sardine larval data from the same surveys suggest that the reduction in mean probability of presence in the north is less marked than for eggs (although this comparison ignores the presence of sardine larvae beyond the continental shelf in the 1980s). Similar changes off northern Portugal and western Galicia are observed in commercial sardine catches and the acoustically estimated area of fish distribution. It is possible that the observed decline in spawning area off northwestern Iberia during the 1990s is indirectly reflecting the prevalence of environmental conditions detrimental to sardine recruitment (northerly winds during winter that favour coastal upwelling and offshore transport), which have reduced the spawning contribution of young fish in that area.

Role of metabolites in MDMA (ecstasy)-induced nephrotoxicity: an in vitro study using rat and human renal proximal tubular cells - Má rcia Carvalho; Gabrielle Hawksworth; Nuno Milhazes; Fernanda Borges; Terrence Monks; Eduarda Fernandes; Fé lix Carvalho; Maria Bastos (Archives of Toxicology, 2002)

Warring ants: Lessons from Lanchester’s laws of combat? - Renee M. Borges (Journal of Biosciences, 2002)

Phagocytosis and giant cell formation at 0° C by macrophage (MØ) of Notothenia coriiceps - J. R. M. C. Silva; N. A. Staines; F. J. Hernandez‐Blazquez; L. R. Porto‐Neto; J. C. S. Borges (Journal of Fish Biology, 2002)
Macrophages adhered to round glass coverslips that had been implanted into the abdominal cavity of Notothenia coriiceps , collected from Admiralty Bay, King George Island, and removed and incubated in vitro for 4 h at 0° C at various intervals. The macrophages phagocytosed yeast Saccharomyces cerevisiae cells suspended in saline. Bi‐nuclear macrophages were first observed after 6 h. The formation of giant cells and their phagocytic activity was observed only in fish which had been injected with 1 ml of Bacillus of Calmette and Guerin (BCG)‐suspension 24 h before coverslip implantation and the coverslips removed 15 days after the implantation. Phagocytosis and the formation of giant cells in an Antarctic fish at 0° C is described for the first time.

A comparative study of the species composition of discards from five fisheries from the Algarve (southern Portugal) - K. ERZINI; M. E. COSTA; L. BENTES; T. C. BORGES (Fisheries Management and Ecology, 2002)
Discards from five of the most important fisheries (crustacean trawling, fish trawling, demersal purse seining, pelagic purse seining and trammel netting) in southern Portugal were studied and compared. A total of 236 species of all taxa were discarded, with fish and cephalopods accounting for more than 90% of the discarded biomass, except trammel nets (81%). Although there was some overlapping of species, multivariate analysis using cluster analysis for classification and multidimensional scaling (MDS) for ordination, showed that there were significant differences between the five gears in terms of species composition and biomasses discarded, with the least similarity between crustacean trawling and all other fishing operations. The differences between fisheries were probably as a result of a combination of gear selectivity and depth fished. The results suggest that discarding practices are likely to have different, yet significant impacts on the marine ecosystem, warranting further studies on the fate of discards, the factors influencing discarding and mitigation.

Why are chillies pungent? - Renee M. Borges (Journal of Biosciences, 2001)

Ant and human farmers face similar problems - Renee M. Borges (Journal of Biosciences, 2001)

Cytokeratin expression in human fetal tongue and buccal mucosa - M M Vaidya; Sharda S. Sawant; Anita M. Borges; N K Naresh; Manda C. Purandare; A N Bhisey (Journal of Biosciences, 2000)

Feverish honeybees - Renee M. Borges (Journal of Biosciences, 2000)

Effect of phenylalanine and p-chlorophenylalanine on Na+, K+-ATPase activity in the synaptic plasma membrane from the cerebral cortex of rats - Emílio L. Streck; Patrícia T. Edom; Maria E. Noriler; Luiz F. Borges; Zilda L. Pontes; Edino Parolo; Carlos S. Dutra-Filho; Clóvis M. D. Wannmacher; Angela T. S. Wyse (Metabolic Brain Disease, 2000)

Clipboard - Renee M. Borges; Vidita A. Vaidya (Journal of Biosciences, 2000)

Impacts of the Time Horizon for Adjacency Constraints in Harvest Scheduling - Howard M. Hoganson; Jose G. Borges (Forest Science, 2000)
Adjacency constraints, constraints which limit the harvest timings of adjacent management units, are a challenge to address within forest management scheduling models. Four large test cases were examined to consider the need to recognize site-specific adjacency constraints over a long time horizon within a forest management scheduling model. Results suggest that the costs of adjacency constraints tend to be short-term in nature. Immediate periods tend to be influenced most because there is less lead time to prepare for the constraints. Little may be gained in planning by addressing adjacency constraints for more than a full rotation length. Adjacency constraints can likely be satisfied efficiently without having large shifts in harvest timings for most all management units. Results are consistent with an interpretation of the dual formulation of a relaxed linear programming formulation of the problem. For. Sci. 46(2):176-187.

Thermococcus waiotapuensis sp. nov., an extremely thermophilic archaeon isolated from a freshwater hot spring - Juan M. González; D. Sheckells; Mareike Viebahn; Donara Krupatkina; Kimberly M. Borges; F. T. Robb (Archives of Microbiology, 1999)

Combining a Decomposition Strategy with Dynamic Programming to Solve Spatially Constrained Forest Management Scheduling Problems - José G. Borges; Howard M. Hoganson; Dietmar W. Rose (Forest Science, 1999)
A decomposition approach to solve the forest management scheduling adjacency problem is developed for application to large forests. Overlapping subproblems amenable to exact dynamic programming solution are solved sequentially. A heuristic is used to define and link subproblems such that near-optimal solutions to the master problem are obtained. Both the contrasting size and the irregular shape of stands complicate the problem of formulating the dynamic programming network. Subproblem size and the sequencing of stands for each corresponding dynamic programming network are defined simultaneously, as model size is especially sensitive to stand sequencing. Emphasis is on efficient dynamic programming formulations to allow for large subproblems. Results from over 100 test computer runs are discussed for applications to 3 large problems. Results suggest that the strategy can consistently produce near-optimal solutions at reasonable computational cost. A procedure is developed to derive three slightly different adjacency problems so that the optimal solution can be found. Results for applications to the modified problems show that the proposed heuristic's solutions were within 0.01, 0.04, and 0.01% of the optimal solution, respectively. The proposed solution method consistently outperformed two other heuristics that were applied. For. Sci. 45(1):201-212.

Pheromone Sharing: Blends Based on the Same Compounds for Euschistus heros and Piezodorus guildinii - Miguel Borges; Paulo H. G. Zarbin; J. Tércio B. Ferreira; Maria L. M. Da Costa (Journal of Chemical Ecology, 1999)

Using Dynamic Programming and Overlapping Subproblems to Address Adjacency in Large Harvest Scheduling Problems - Howard M. Hoganson; Jose G. Borges (Forest Science, 1998)
The adjacency problem for forest management scheduling is formulated as a dynamic programming problem. To overcome typical model-size problems, a solution strategy is proposed which links dynamic programming formulations for overlapping subproblems. Subproblems are solved sequentially in a moving-windows fashion. Solutions are near-optimal for three large but simplified test cases. Model size is sensitive to the size of the moving window. Using relatively small windows produced solutions that are closer to optimal than those found using two other modeling approaches. Solutions are also insensitive to the side of the forest used to start the moving-windows process, and microcomputer solution times are not a major consideration. The strategy offers potential to treat adjacency measures as valued management outputs. It will likely fit well into broader forestwide models which decompose the forestwide problem into parts to help address other forestwide constraints. For. Sci. 44(4):526-538.

CpG-containing oligodeoxynucleotides as new generation adjuvants in DNA and protein vaccines - Rajiv K. Saxena; Saubiya M. Siddiqui; Renee M. Borges (Journal of Biosciences, 1998)